Lithographic printing plate precursor, method for preparing a lithographic printing plate, and lithographic printing method

The lithographic printing plate precursor with an image recording layer containing addition polymerization resin and hydrogen bond-donating sites addresses the challenge of printing resistance with UV ink, achieving enhanced performance and suitability for on-machine development.

JP7669148B2Active Publication Date: 2025-04-28FUJIFILM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020569404
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-01-31
Filing Date
2019-11-27
Publication Date
2025-04-28
Estimated Expiration
2039-11-27

AI Technical Summary

Technical Problem

Existing lithographic printing plate precursors lack sufficient printing resistance when using UV ink, and there is a need for a method to prepare lithographic printing plates that can handle UV ink effectively.

Method used

A lithographic printing plate precursor is developed with a support and an image recording layer containing organic particles with an addition polymerization resin. The resin has a structural unit A with a hydrogen bond-donating site, with a content greater than 20% by mass, providing enhanced hardness and strength to the image recording layer.

Benefits of technology

The lithographic printing plate precursor achieves excellent printing resistance, even with UV ink, due to the increased hardness and strength of the image recording layer, and is suitable for on-machine development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669148000001
    Figure 0007669148000001
  • Figure 0007669148000002
    Figure 0007669148000002
  • Figure 0007669148000003
    Figure 0007669148000003
Patent Text Reader

Abstract

A lithographic printing plate precursor comprising a support and an image recording layer on the support, the image recording layer containing organic particles comprising an addition polymerization resin having a structural unit A having a hydrogen bond donor site, and the content of the structural unit A in the addition polymerization resin is more than 20 mass % relative to the total mass of the addition polymerization resin; and a method for producing a lithographic printing plate using the lithographic printing plate precursor.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a lithographic printing plate precursor, a method for preparing a lithographic printing plate, and a lithographic printing method. [Background technology]

[0002] Generally, a lithographic printing plate consists of an oleophilic image area that accepts ink during the printing process, and a hydrophilic non-image area that accepts dampening water. Lithographic printing utilizes the mutual repulsion properties of water and oil-based ink, making the oleophilic image area of ​​the lithographic printing plate the ink-receptive area and the hydrophilic non-image area the dampening water-receptive area (ink-non-receptive area) to create a difference in ink adhesion on the surface of the lithographic printing plate, and after ink is applied only to the image area, the ink is transferred to the printing material such as paper to print. To prepare such a lithographic printing plate, a lithographic printing plate precursor (PS plate) having an oleophilic photosensitive resin layer (image recording layer) on a hydrophilic support has been widely used. Usually, the lithographic printing plate precursor is exposed to light through an original such as a lithographic film, and then the image areas of the image recording layer are left, while the other unnecessary image recording layer is dissolved and removed with an alkaline developer or organic solvent, exposing the hydrophilic support surface to form non-image areas, thereby obtaining a lithographic printing plate.

[0003] Furthermore, due to growing concern about the global environment, environmental issues related to waste liquids accompanying wet processing such as development processing have come into focus. In response to the above environmental issues, efforts are being made to simplify development or plate making, or to eliminate any processing. One of the simple manufacturing methods is a method called "on-press development." In other words, after exposing a lithographic printing plate precursor to light, it is mounted on a printing press as is, without undergoing conventional development, and unnecessary parts of the image recording layer are removed at an early stage of the normal printing process.

[0004] Conventional lithographic printing plate precursors include those described in Patent Documents 1 and 2, for example. Patent Document 1 describes a lithographic printing plate precursor having an image recording layer on a support, the image recording layer containing an infrared absorbing agent, a polymerization initiator, a polymerizable compound having a hydrogen bonding group, and hard polymer particles having at least one group selected from the group consisting of a urethane group, a urea group, an imide group, an amide group, and a sulfonamide group on the surface thereof, the hard polymer particles having a number average primary particle size of 0.01 to 1 μm.

[0005] Patent Document 2 describes a lithographic printing plate precursor having a support and a hydrophilic layer containing particles to which a hydrophilic polymer is bonded and a hydrophilic-hydrophobic converting agent that acts upon the application of thermal energy, characterized in that the hydrophilic polymer is bonded to the particles at one end and the particles are chemically bonded to each other.

[0006] Patent Document 1: International Publication No. 2017 / 150039 Patent Document 2: JP 2006-315265 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a lithographic printing plate precursor that is excellent in printing durability even when UV ink is used. Another object of the present invention is to provide a method for producing a lithographic printing plate or a lithographic printing method using the above-mentioned lithographic printing plate precursor. [Means for solving the problem]

[0008] Means for solving the above problems include the following aspects. <1> A lithographic printing plate precursor comprising: a support; and an image recording layer on the support, the image recording layer containing organic particles including an addition polymerization resin having a structural unit A having a hydrogen bond donor site, the content of the structural unit A in the addition polymerization resin being more than 20 mass % relative to the total mass of the addition polymerization resin. <2> The content of the structural unit A in the addition polymerization resin is 25% by mass or more based on the total mass of the addition polymerization resin. <1> The lithographic printing plate precursor according to claim 1. <3> The addition polymerization type resin further has a structural unit having an aromatic ring. <1> or <2> The lithographic printing plate precursor according to claim 1. <4> The addition polymerization resin further has a structural unit having the hydrophilic group. <1> ~ <3> 10. The lithographic printing plate precursor according to claim 9, <5> The hydrophilic group is an ionic group or a group having a polyalkylene oxide structure. <4> The planographic printing plate precursor according to <6> The hydrophilic group is a group represented by the following formula Z: <4> The lithographic printing plate precursor according to claim 1. -QWY formula Z In formula Z, Q represents a divalent linking group, W represents a divalent group having a hydrophilic structure or a divalent group having a hydrophobic structure, and Y represents a monovalent group having a hydrophilic structure or a monovalent group having a hydrophobic structure, with the proviso that either W or Y has a hydrophilic structure. <7> The hydrophilic group is a group having a polyalkylene oxide structure. <4> The lithographic printing plate precursor according to claim 1. <8> The hydrophilic group is a sulfonate group or a sulfonic acid group. <4> The lithographic printing plate precursor according to claim 1. <9> The content of the structural unit having the hydrophilic group in the addition polymerization resin is 1% by mass to 20% by mass with respect to the total mass of the addition polymerization resin. <4> ~ <8> 10. The lithographic printing plate precursor according to claim 9, <10> The organic particles include organic particles having ethylenically unsaturated groups on the surface. <1> ~ <9> 10. The lithographic printing plate precursor according to claim 9, <11> The image recording layer further comprises an infrared absorbing agent. <1> ~ <10> 10. The lithographic printing plate precursor according to claim 9, <12> The image recording layer further contains a polymerization initiator and a polymerizable compound. <1> ~ <11> 10. The lithographic printing plate precursor according to claim 9, <13> The image recording layer further comprises a binder polymer. <1> ~ <12> 10. The lithographic printing plate precursor according to claim 9, <14> A protective layer is further provided on the image recording layer. <1> ~ <13> 10. The lithographic printing plate precursor according to claim 9, <15> The protective layer contains an inorganic layered compound. <14> The lithographic printing plate precursor according to claim 1. <16> The image recording layer is a negative image recording layer. <1> ~ <15> 10. The lithographic printing plate precursor according to claim 9, <17> The image recording layer is an on-machine development type image recording layer. <1> ~ <16> 10. The lithographic printing plate precursor according to claim 9, <18> <1> ~ <17> and supplying at least one selected from the group consisting of a printing ink and a fountain solution to remove the image recording layer in a non-image area on a printing press. <19> <1> ~ <17> a step of imagewise exposing the lithographic printing plate precursor according to any one of the above items 1 to 5; a step of removing the image recording layer in non-image areas on a printing press by supplying at least one selected from the group consisting of a printing ink and a fountain solution to prepare a lithographic printing plate; and a step of printing with the obtained lithographic printing plate. Effect of the Invention

[0009] According to an embodiment of the present invention, it is possible to provide a lithographic printing plate precursor that is excellent in printing durability even when UV ink is used. According to another embodiment of the present invention, there can be provided a method for producing a lithographic printing plate or a lithographic printing method using the above-mentioned lithographic printing plate precursor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The contents of the present disclosure will be described in detail below. The following description of the components may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment. In this specification, the use of "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower limit and upper limit. In addition, in the description of groups (atomic groups) in this specification, descriptions that do not indicate whether they are substituted or unsubstituted include those that have no substituents as well as those that have a substituent. For example, an "alkyl group" includes not only an alkyl group that has no substituents (unsubstituted alkyl groups) but also an alkyl group that has a substituent (substituted alkyl groups). In this specification, "(meth)acrylic" is a term used as a concept including both acrylic and methacrylic, and "(meth)acryloyl" is a term used as a concept including both acryloyl and methacryloyl. In addition, the term "step" in this specification includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. In addition, in this disclosure, "mass %" and "weight %" are synonymous, and "parts by mass" and "parts by weight" are synonymous. Furthermore, in the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In addition, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) in the present disclosure are molecular weights detected by a gel permeation chromatography (GPC) analyzer using columns of TSKgel GMHxL, TSKgel G4000HxL, or TSKgel G2000HxL (all product names manufactured by Tosoh Corporation) in a solvent of THF (tetrahydrofuran) and a differential refractometer, and converted using polystyrene as a standard substance. In this specification, the term "lithographic printing plate precursor" includes not only lithographic printing plate precursors but also throwaway plate precursors. Furthermore, the term "lithographic printing plate" includes not only lithographic printing plates prepared by subjecting a lithographic printing plate precursor to operations such as exposure and development as necessary, but also throwaway plates. In the case of a throwaway plate precursor, the operations of exposure and development are not necessarily required. Note that a throwaway plate is a lithographic printing plate precursor that is attached to an unused plate cylinder when, for example, a portion of the page is printed in one color or two colors in color newspaper printing. The present disclosure will be described in detail below.

[0011] (lithographic printing plate original plate) The lithographic printing plate precursor according to the present disclosure has a support and an image recording layer on the support, the image recording layer containing organic particles including an addition polymerization resin having a structural unit A having a hydrogen bond donor site, and the content of the structural unit A in the addition polymerization resin is more than 20 mass % relative to the total mass of the addition polymerization resin. Furthermore, the lithographic printing plate precursor according to the present disclosure may be either a negative-working lithographic printing plate precursor or a positive-working lithographic printing plate precursor, but is preferably a negative-working lithographic printing plate precursor. Furthermore, the lithographic printing plate precursor according to the present disclosure can be suitably used as a lithographic printing plate precursor for on-press development.

[0012] As a result of extensive research, the inventors have found that by adopting the above-mentioned configuration, it is possible to provide a lithographic printing plate precursor which can produce a lithographic printing plate having excellent printing durability (UV printing durability) even when ultraviolet-curable ink (UV ink) is used. Although the detailed mechanism by which the above effects are obtained is unclear, it is speculated as follows. It is presumed that the image recording layer contains organic particles including an addition polymerization resin having a structural unit A having a hydrogen bond donor site, and the content of the structural unit A in the addition polymerization resin is more than 20 mass % relative to the total mass of the addition polymerization resin, thereby increasing the hardness of the organic particles and enabling the production of image areas with excellent strength, resulting in excellent printing durability (UV printing durability) even when UV ink is used.

[0013] Furthermore, since the image recording layer contains organic particles including an addition polymerization resin having a structural unit A having a hydrogen bond donor site, and the content of the structural unit A in the addition polymerization resin is more than 20 mass % relative to the total mass of the addition polymerization resin, the hardness of the organic particles is increased, the strength of the image recording layer is excellent, and the dispersibility of the organic particles in the image recording layer is also excellent, so that the lithographic printing plate precursor according to the present disclosure is presumed to also have excellent scratch resistance.

[0014] <Image recording layer> The lithographic printing plate precursor according to the present disclosure has an image recording layer on a support, the image recording layer contains organic particles including an addition polymerization resin having a structural unit A having a hydrogen bond donor site, and the content of the structural unit A in the addition polymerization resin is more than 20 mass % relative to the total mass of the addition polymerization resin. The image recording layer used in the present disclosure is preferably a negative image recording layer, and more preferably a water-soluble or water-dispersible negative image recording layer. In addition, from the viewpoints of printing durability and photosensitivity, the image recording layer used in the present disclosure preferably further contains a polymerization initiator and a polymerizable compound, and preferably further contains an electron-accepting polymerization initiator and a polymerizable compound. Furthermore, the image recording layer used in the present disclosure is preferably an on-press development type image recording layer. Each component contained in the image recording layer will be described in detail below.

[0015] -Organic particles containing an addition polymerization type resin having a structural unit A having a hydrogen bond donor site- The image recording layer in the lithographic printing plate precursor according to the present disclosure contains organic particles (also referred to as "specific particles") that contain an addition polymerization resin having a structural unit A that has a hydrogen bond donor site.

[0016] The hydrogen bond donor site in the structural unit A having the hydrogen bond donor site may have any structure as long as it has an active hydrogen atom capable of forming a hydrogen bond, and is preferably a structure represented by XH. X represents a heteroatom, and is preferably a nitrogen atom or an oxygen atom. From the viewpoint of UV printing durability and scratch resistance, the hydrogen bond donor site is preferably at least one structure selected from the group consisting of a hydroxyl group, a carboxyl group, a primary amide group, a secondary amide group, a primary amino group, a secondary amino group, a primary sulfonamide group, a secondary sulfonamide group, an imide group, a urea bond, and a urethane bond, more preferably at least one structure selected from the group consisting of a hydroxyl group, a carboxyl group, a primary amide group, a secondary amide group, a primary sulfonamide group, a secondary sulfonamide group, a maleimide group, a urea bond, and a urethane bond, even more preferably at least one structure selected from the group consisting of a hydroxyl group, a carboxyl group, a primary amide group, a secondary amide group, a primary sulfonamide group, a secondary sulfonamide group, and a maleimide group, and particularly preferably at least one structure selected from the group consisting of a hydroxyl group and a secondary amide group. The structural unit A may have only one type of the hydrogen bond donor site, or may have two or more types.

[0017] The structural unit A may have a hydrogen bond accepting site, and from the viewpoints of UV printing durability and scratch resistance, it preferably has a hydrogen bond accepting site. The hydrogen bond accepting site may be any structure containing an atom having an unshared electron pair, but from the viewpoint of UV printing durability and scratch resistance, it is preferably a structure containing an oxygen atom having an unshared electron pair, more preferably at least one structure selected from the group consisting of a carbonyl group (including carbonyl structures such as a carboxy group, an amide group, an imide group, a urea bond, and a urethane bond) and a sulfonyl group (including sulfonyl structures such as a sulfonamide group), and particularly preferably a carbonyl group (including carbonyl structures such as a carboxy group, an amide group, an imide group, a urea bond, and a urethane bond). In the present disclosure, the hydrogen bond accepting moiety does not include a hydroxy group. Although a hydroxy group is a group that has excellent hydrogen bond donating properties as the hydrogen bond donating moiety, the hydrogen bond accepting property of the oxygen atom of the hydroxy group is smaller than that of the above-mentioned structure, and from the viewpoint of UV printing durability, the hydroxy group is defined as the hydrogen bond donating moiety in the present disclosure. Furthermore, the structural unit A may have only one type of the hydrogen bond accepting site, or may have two or more types. Furthermore, from the viewpoint of UV printing resistance and scratch resistance, as described above, the structural unit A preferably has a carboxy group, an amide group, an imide group, a urea bond, a urethane bond, or a sulfonamide group, which is the hydrogen bond donor site and a hydrogen bond acceptor site, and more preferably has a carboxy group, an amide group, an imide group, or a sulfonamide group. Moreover, the above-mentioned structural unit A is preferably a structural unit having a nitrogen atom.

[0018] Preferred examples of the monomer that forms the structural unit A include monomers having a hydrogen bond donor site, more preferred examples include (meth)acrylate compounds having a hydrogen bond donor site, (meth)acrylamide compounds having a hydrogen bond acceptor site, and maleimide compounds having a hydrogen bond donor site, and particularly preferred examples include (meth)acrylate compounds having a hydrogen bond donor site, and (meth)acrylamide compounds having a hydrogen bond acceptor site. The monomer may be a monovalent monomer or a divalent or higher monomer. Furthermore, the monomer is preferably an ethylenically unsaturated compound. The number of carbon atoms in the structural unit A is not particularly limited, but is preferably 5 or more, more preferably 5 to 30, and particularly preferably 6 to 20, from the viewpoints of UV printing durability and scratch resistance.

[0019] Preferred specific examples of the structural unit A include those shown below, but needless to say, are not limited to these. First, specific examples of the structural unit A having both the hydrogen bond donor site and the hydrogen bond acceptor site will be shown.

[0020] [ka]

[0021] Specific examples of the structural unit A having only the above hydrogen bond donor site are shown below.

[0022] [ka]

[0023] The addition polymerization resin may have one type of the structural unit A alone, or two or more types. The content of the structural unit A in the addition polymerization resin is more than 20% by mass, based on the total mass of the addition polymerization resin, and from the viewpoints of UV printing durability and scratch resistance, is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 30 to 90% by mass, and particularly preferably 35 to 80% by mass.

[0024] The addition polymerization resin may have a structural unit other than the structural unit A. From the viewpoints of suppressing development residue, UV printing durability, and scratch resistance, it is preferable that the addition polymerization resin further contains a structural unit having a hydrophilic group other than the structural unit A. From the viewpoints of development residue suppression, UV printing durability, and scratch resistance, the hydrophilic group is preferably an ionic group, a group having a polyalkylene oxide structure, a group having a polyester structure, or a sulfonic acid group, more preferably an ionic group, a group having a polyalkylene oxide structure, or a sulfonic acid group, more preferably a sulfonate salt group, a group having a polyalkylene oxide structure, or a sulfonic acid group, and particularly preferably a sulfonate salt group or a sulfonic acid group. From the viewpoints of particle dispersibility, UV printing durability, and scratch resistance, the hydrophilic group is particularly preferably a group having a polyalkylene oxide structure. From the viewpoints of UV printing durability and scratch resistance, the addition polymerization resin preferably has an ionic group, and more preferably has a sulfonate group.

[0025] Examples of the ionic group include an anionic group, a cationic group, and a group having a betaine structure. The anionic group is preferably a sulfonate group or a carboxylate group, and more preferably a sulfonate group. Sulfonate group (-SO3M C ) or carboxylate group (-COOM C ) counter cation M C Although there is no particular limitation, alkali metal cations are preferred. C may be a monovalent cation or a divalent or higher cation, so long as it is electrically neutralized. The cationic group is an ammonium salt (-NR A 4M A ) is preferably the counter anion M of the ammonium salt group. A Although there is no particular limitation, a sulfonate anion or a carboxylate anion is preferable. A may be a monovalent anion or a divalent or higher anion, so long as it is electrically neutralized.

[0026] From the viewpoint of on-press developability, the polyalkylene oxide structure is preferably a polyethylene oxide structure, a polypropylene oxide structure, or a poly(ethylene oxide / propylene oxide) structure. The number of alkylene oxide structures in the polyalkylene oxide structure is preferably 2 or more, more preferably 5 or more, further preferably 5 to 200, and particularly preferably 8 to 150, from the viewpoint of on-press developability.

[0027] The polyester structure is not particularly limited, but preferred examples include a ring-opening polymerization chain of lactone and a polycondensation chain of hydroxycarboxylic acid. The number of hydroxycarboxylic acid structures (lactone structures) in the polyester structure is preferably 2 or more, more preferably 2 to 20, further preferably 2 to 10, and particularly preferably 4 to 10, from the viewpoint of on-machine developability.

[0028] From the viewpoints of UV printing durability and on-press developability, the addition polymerization resin preferably has a constitutional unit represented by the following formula (C).

[0029] [ka]

[0030] In formula C, L 1c represents an ethylene group or a propylene group, R 1c represents a hydrogen atom, an alkyl group, or an aryl group; R 2c represents a hydrogen atom or a methyl group, and mc represents an integer of 2 to 200.

[0031] L 1c is preferably an ethylene group or a 1,2-propylene group. R 1c is preferably a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a phenyl group, more preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and more preferably a hydrogen atom or a methyl group. mc is preferably an integer of 2-200, more preferably an integer of 2-100, and further preferably an integer of 2-50.

[0032] From the viewpoint of on-press developability, the hydrophilic group is preferably a group represented by the following formula Z: Furthermore, from the viewpoint of on-machine developability, the addition polymerization resin preferably has a structural unit having a group represented by the following formula Z. -QWY formula Z In formula Z, Q represents a divalent linking group, W represents a divalent group having a hydrophilic structure or a divalent group having a hydrophobic structure, and Y represents a monovalent group having a hydrophilic structure or a monovalent group having a hydrophobic structure, with the proviso that either W or Y has a hydrophilic structure.

[0033] Q is preferably a divalent linking group having 1 to 20 carbon atoms, and more preferably a divalent linking group having 1 to 10 carbon atoms. Furthermore, Q is preferably an alkylene group, an arylene group, an ester bond, an amide bond, or a group consisting of a combination of two or more of these, and more preferably a phenylene group, an ester bond, or an amide bond.

[0034] The divalent group having a hydrophilic structure in W is a polyalkyleneoxy group or a polyalkyleneoxy group having -CH2CH2NR at one end. W It is preferable that R W represents a hydrogen atom or an alkyl group. The divalent group having a hydrophobic structure in W is -R WA -, -OR WA -O-, -R W NR WA -NR W -, -OOC-R WA -O- or -OOC-R WA It is preferable that R is —O—. WA each independently represents a linear, branched, or cyclic alkylene group having 6 to 120 carbon atoms, a haloalkylene group having 6 to 120 carbon atoms, an arylene group having 6 to 120 carbon atoms, an alkylylene group having 6 to 120 carbon atoms (a divalent group obtained by removing one hydrogen atom from an alkylaryl group), or an aralkylene group having 6 to 120 carbon atoms.

[0035] The monovalent group having a hydrophilic structure in Y is OH, COOH, a polyalkyleneoxy group having a hydrogen atom or an alkyl group at the end, or a polyalkyleneoxy group having a hydrogen atom or an alkyl group at the other end, and -CH2CH2N(R W It is preferable that the aryl group is a group having a bond with . The monovalent group having a hydrophobic structure for Y is a linear, branched or cyclic alkyl group having 6 to 120 carbon atoms, a haloalkyl group having 6 to 120 carbon atoms, an aryl group having 6 to 120 carbon atoms, an alkaryl group (alkylaryl group) having 6 to 120 carbon atoms, an aralkyl group having 6 to 120 carbon atoms, OR WB , COOR WB , or OOCR WB It is preferable that R WB represents an alkyl group having 6 to 20 carbon atoms.

[0036] Preferred specific examples of the structural unit having a hydrophilic group include those shown below, but needless to say are not limited to these. Here, nc represents an integer of 2 or more, and is preferably an integer of 2-200. Also, C 10 ~C 14 represents an alkyl group having 10 to 14 carbon atoms, and may be a mixture of compounds having these groups.

[0037] [ka]

[0038] The addition polymerization resin may have one type of structural unit having a hydrophilic group, or may have two or more types of structural units having a hydrophilic group. From the viewpoint of on-machine developability, the content of the structural unit having a hydrophilic group is preferably 0.5% by mass to 40% by mass, more preferably 1% by mass to 30% by mass, and particularly preferably 2% by mass to 25% by mass, relative to the total mass of the addition polymerization resin.

[0039] From the viewpoints of UV printing durability and scratch resistance, it is preferable that the addition polymerization resin further has a structural unit other than the structural unit A that has an aromatic ring. The aromatic ring may be an aromatic hydrocarbon ring, a heteroaromatic ring, or a condensed ring thereof, but is preferably an aromatic hydrocarbon ring, and more preferably a benzene ring. There are no particular limitations on the number of aromatic rings in the aromatic ring-containing structural unit, but it is preferably 1 to 4, more preferably 1 or 2, and particularly preferably 1.

[0040] Preferred examples of the monomer that forms the structural unit having an aromatic ring include a styrene compound, a (meth)acrylate compound having an aromatic ring, and a (meth)acrylamide compound having an aromatic ring. The monomer may be a monovalent monomer or a divalent or higher monomer. Furthermore, the monomer is preferably an ethylenically unsaturated compound. The number of carbon atoms in the aromatic ring-containing structural unit is not particularly limited, but is preferably 8 or more, more preferably 8 to 30, and particularly preferably 8 to 20, from the viewpoints of UV printing durability and scratch resistance.

[0041] Preferred specific examples of the structural unit having an aromatic ring include those shown below, but needless to say are not limited to these.

[0042] [ka]

[0043] The addition polymerization resin may have one type of aromatic ring-containing structural unit alone or two or more types of aromatic ring-containing structural units. From the viewpoint of on-machine developability, the content of the structural unit having an aromatic ring is preferably 10% by mass to 90% by mass, more preferably 20% by mass to 80% by mass, and particularly preferably 35% by mass to 75% by mass, relative to the total mass of the addition polymerization resin.

[0044] The addition polymerization resin may have a structural unit (another structural unit) other than the structural units described above. As the other structural units, structural units having a hydrogen bond accepting site are preferably used. Preferred examples of compounds that form other structural units include ethylenically unsaturated compounds such as styrene compounds, (meth)acrylate compounds, (meth)acrylamide compounds, (meth)acrylonitrile compounds, vinyl halide compounds, vinyl ester compounds, vinyl ether compounds, and α-olefin compounds.

[0045] The addition polymerization resin may have one type of other structural unit alone, two or more types of other structural units, or may not have any other structural units. From the viewpoints of UV printing durability and on-press developability, the content of other structural units in the addition polymerization resin is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less, relative to the total mass of the addition polymerization resin.

[0046] The weight average molecular weight (Mw) of the addition polymerization resin is not particularly limited, but is preferably 2,000 or more, more preferably 5,000 or more, and even more preferably 10,000 to 2,000,000.

[0047] The specific particles may contain one type of the addition polymerization resin alone or two or more types of the resin. From the viewpoint of UV printing resistance and scratch resistance, the content of the above-mentioned addition polymerization type resin in the specific particles is preferably 50 mass% or more, more preferably 60 mass% or more, and particularly preferably 70 mass% to 100 mass%, relative to the total mass of the specific particles.

[0048] In addition, the specific particles are preferably surface-modified particles. The surface modification method is not particularly limited, and any known method can be used, such as a method of reacting a compound having a reactive group with the particle surface, or a method of coating the particle surface with a compound such as a polymer. Suitable examples of the reactive group include an epoxy group and an oxetanyl group. Since the specific particles have a hydrogen bond donor site, it is also preferable to coat the particle surface with a polymer having a hydrogen bond acceptor site or a polymer having both a hydrogen bond acceptor site and a hydrogen bond donor site.

[0049] From the viewpoints of UV printing durability and on-press developability, the specific particles preferably include particles having a polymerizable group on the surface, and more preferably include particles having an ethylenically unsaturated group on the surface. A preferred method for introducing a polymerizable group such as an ethylenically unsaturated group onto the particle surface is, for example, a method in which a compound having an ethylenically unsaturated group and an epoxy group is reacted with a hydroxy group or the like present on the particle surface. In addition, from the viewpoints of UV printing durability and scratch resistance, the specific particles are preferably particles having a crosslinked structure.

[0050] From the viewpoints of developability, UV printing durability, and scratch resistance, the volume average particle size of the specific particles is preferably 10 nm to 1,000 nm, more preferably 20 nm to 500 nm, even more preferably 50 nm to 300 nm, and particularly preferably 70 nm to 200 nm. The average particle size of each particle in the present disclosure is measured by a light scattering method, or by taking an electron microscope photograph of the particles, measuring the particle sizes of 5,000 particles in total on the photograph, and calculating the average value. Note that for non-spherical particles, the particle size is the particle size value of a spherical particle having the same particle area as the particle area on the photograph. In addition, the average particle size in this disclosure is taken to be the volume average particle size unless otherwise specified.

[0051] Suitable specific examples of the addition polymerization resin and specific particles used in the present disclosure include those used in the examples described below, but needless to say, are not limited to these.

[0052] The image recording layer may contain one type of specific particles alone or two or more types of specific particles. From the viewpoints of UV printing durability and scratch resistance, the content of the specific particles is preferably 10% by mass to 70% by mass, more preferably 20% by mass to 65% by mass, and particularly preferably 30% by mass to 65% by mass, relative to the total mass of the image recording layer.

[0053] -Infrared absorbent- The image recording layer preferably further contains an infrared absorbing agent. Infrared absorbers include pigments and dyes. As the dye to be used as the infrared absorber, commercially available dyes and known dyes described in literature such as "Dye Handbook" (edited by the Organic Synthesis Chemistry Association, published in 1970) can be used. Specific examples of the dye include azo dyes, metal complex azo dyes, pyrazolone azo dyes, naphthoquinone dyes, anthraquinone dyes, phthalocyanine dyes, carbonium dyes, quinoneimine dyes, methine dyes, cyanine dyes, squarylium dyes, pyrylium salts, and metal thiolate complex dyes. Particularly preferred among these dyes are cyanine dyes, squarylium dyes, pyrylium salts, nickel thiolate complexes, and indolenine cyanine dyes.Furthermore, cyanine dyes and indolenine cyanine dyes are also included.Of these, cyanine dyes are particularly preferred.

[0054] Specific examples of cyanine dyes include the compounds described in paragraphs 0017 to 0019 of JP-A-2001-133969, the compounds described in paragraphs 0016 to 0021 of JP-A-2002-023360, and the compounds described in paragraphs 0012 to 0037 of JP-A-2002-040638, preferably the compounds described in paragraphs 0034 to 0041 of JP-A-2002-278057, and the compounds described in paragraphs 0080 to 0086 of JP-A-2008-195018, and particularly preferably the compounds described in paragraphs 0035 to 0043 of JP-A-2007-90850, and the compounds described in paragraphs 0105 to 0113 of JP-A-2012-206495. In addition, the compounds described in paragraphs 0008 to 0009 of JP-A No. 5-5005 and paragraphs 0022 to 0025 of JP-A No. 2001-222101 can also be preferably used. As the pigment, the compounds described in paragraphs 0072 to 0076 of JP-A No. 2008-195018 are preferred. In addition, infrared absorbing agents that decompose when exposed to infrared rays (also called "decomposable infrared absorbing agents") can also be suitably used. As the infrared absorbent that decomposes upon exposure to infrared rays, those described in JP-T-2008-544322, WO 2016 / 027886, WO 2017 / 141882, or WO 2018 / 043259 can be suitably used.

[0055] The infrared absorbing agent may be used alone or in combination of two or more kinds. Also, a pigment and a dye may be used in combination as the infrared absorbing agent. The content of the infrared absorbing agent in the image recording layer is preferably from 0.1% by mass to 10.0% by mass, and more preferably from 0.5% by mass to 5.0% by mass, based on the total mass of the image recording layer.

[0056] -Polymerization initiator- The image recording layer in the lithographic printing plate precursor according to the present disclosure preferably further contains a polymerization initiator, and more preferably further contains a polymerization initiator and a polymerizable compound. The polymerization initiator preferably contains an electron-accepting polymerization initiator.

[0057] <<Electron-accepting polymerization initiator>> The image recording layer preferably contains an electron-accepting polymerization initiator (also called a "polymerization auxiliary") as a polymerization initiator. The electron-accepting polymerization initiator is a compound that generates a polymerization initiating species such as a radical by accepting one electron through intermolecular electron transfer when electrons of an infrared absorbing agent are excited by exposure to infrared light. The electron-accepting polymerization initiator used in the present disclosure is a compound that generates a polymerization initiating species such as a radical or a cation by the energy of light, heat, or both, and can be appropriately selected from known thermal polymerization initiators, compounds having a bond with small bond dissociation energy, photopolymerization initiators, and the like. As the electron-accepting polymerization initiator, a radical polymerization initiator is preferable, and an onium salt compound is more preferable. The electron-accepting polymerization initiator is preferably an infrared-sensitive polymerization initiator. Examples of the electron-accepting radical polymerization initiator include (a) organic halides, (b) carbonyl compounds, (c) azo compounds, (d) organic peroxides, (e) metallocene compounds, (f) azide compounds, (g) hexaarylbiimidazole compounds, (i) disulfone compounds, (j) oxime ester compounds, and (k) onium salt compounds.

[0058] As the (a) organic halide, for example, the compounds described in paragraphs 0022 to 0023 of JP-A No. 2008-195018 are preferable. As the (b) carbonyl compound, for example, the compound described in paragraph 0024 of JP-A-2008-195018 is preferable. As the (c) azo compound, for example, the azo compounds described in JP-A-8-108621 can be used. (d) As the organic peroxide, for example, the compound described in paragraph 0025 of JP-A-2008-195018 is preferable. (e) As the metallocene compound, for example, the compound described in paragraph 0026 of JP-A-2008-195018 is preferable. (f) Examples of the azide compounds include 2,6-bis(4-azidobenzylidene)-4-methylcyclohexanone. (g) Preferred examples of the hexaarylbiimidazole compound include the compounds described in paragraph 0027 of JP-A-2008-195018. (i) Examples of the disulfone compound include the compounds described in JP-A-61-166544 and JP-A-2002-328465. As the (j) oxime ester compound, for example, the compounds described in paragraphs 0028 to 0030 of JP-A No. 2008-195018 are preferable.

[0059] Among the electron-accepting polymerization initiators, preferred from the viewpoint of curability are oxime ester compounds and onium salt compounds. Among them, from the viewpoint of printing durability, preferred are iodonium salt compounds, sulfonium salt compounds and azinium salt compounds, more preferred are iodonium salt compounds and sulfonium salt compounds, and particularly preferred are iodonium salt compounds. Specific examples of these compounds are shown below, but the present disclosure is not limited thereto.

[0060] Preferred examples of the iodonium salt compound include diaryliodonium salt compounds, more preferred are diphenyliodonium salt compounds substituted with electron-donating groups such as alkyl groups or alkoxy groups, and more preferred are asymmetric diphenyliodonium salt compounds. Specific examples include diphenyliodonium hexafluorophosphate, 4-methoxyphenyl-4-(2-methylpropyl)phenyliodonium hexafluorophosphate, 4-(2-methylpropyl)phenyl-p-tolyliodonium hexafluorophosphate, 4-hexyloxyphenyl-2,4,6-trimethoxyphenyliodonium hexafluorophosphate, 4-hexyloxyphenyl-2,4-diethoxyphenyliodonium tetrafluoroborate, 4-octyloxyphenyl-2,4,6-trimethoxyphenyliodonium 1-perfluorobutanesulfonate, 4-octyloxyphenyl-2,4,6-trimethoxyphenyliodonium hexafluorophosphate, and bis(4-t-butylphenyl)iodonium hexafluorophosphate.

[0061] As an example of the sulfonium salt compound, a triarylsulfonium salt compound is preferred, particularly a triarylsulfonium salt compound in which at least a part of the electron-withdrawing group, for example, the group on the aromatic ring, is substituted with a halogen atom, and more preferably a triarylsulfonium salt compound in which the total number of halogen atoms substituted on the aromatic ring is 4 or more. Specific examples include triphenylsulfonium hexafluorophosphate, triphenylsulfonium benzoylformate, bis(4-chlorophenyl)phenylsulfonium benzoylformate, bis(4-chlorophenyl)-4-methylphenylsulfonium tetrafluoroborate, tris(4-chlorophenyl)sulfonium 3,5-bis(methoxycarbonyl)benzenesulfonate, tris(4-chlorophenyl)sulfonium hexafluorophosphate, and tris(2,4-dichlorophenyl)sulfonium hexafluorophosphate.

[0062] As the counter anion of the iodonium salt compound and the sulfonium salt compound, a sulfonamide anion or a sulfonimide anion is preferable, and a sulfonimide anion is more preferable. The sulfonamide anion is preferably an arylsulfonamide anion. The sulfonimide anion is preferably a bisarylsulfonimide anion. Specific examples of sulfonamide anions or sulfonimide anions are shown below, but the present disclosure is not limited thereto. In the following specific examples, Ph represents a phenyl group, Me represents a methyl group, and Et represents an ethyl group.

[0063] [ka]

[0064] The electron-accepting polymerization initiator may be used alone or in combination of two or more kinds. The content of the electron-accepting polymerization initiator is preferably 0.1% by mass to 50% by mass, more preferably 0.5% by mass to 30% by mass, and particularly preferably 0.8% by mass to 20% by mass, based on the total mass of the image recording layer.

[0065] <<Electron-donating polymerization initiator (polymerization aid)>> The image recording layer preferably contains, as a polymerization initiator, an electron-donating polymerization initiator (also called a "polymerization aid"), and more preferably contains an electron-accepting polymerization initiator and a polymerization aid. The electron-donating polymerization initiator in the present disclosure is a compound that, when an electron of an infrared absorber is excited or moves intramolecularly by exposure to infrared light, donates one electron to an orbital of the infrared absorber from which one electron has been lost through intermolecular electron transfer, thereby generating a polymerization initiating species such as a radical. The electron-donating polymerization initiator is preferably an electron-donating radical polymerization initiator. From the viewpoint of improving the printing durability of the lithographic printing plate, the image recording layer more preferably contains an electron-donating polymerization initiator as described below, examples of which include the following five types. (i) Alkyl or aryl ate complexes: It is believed that the carbon-hetero bond is oxidatively cleaved to generate an active radical. Specifically, borate compounds are preferred. (ii) N-arylalkylamine compounds: It is believed that the CX bond on the carbon adjacent to the nitrogen is cleaved by oxidation to generate an active radical. X is preferably a hydrogen atom, a carboxyl group, a trimethylsilyl group, or a benzyl group. Specific examples include N-phenylglycines (which may or may not have a substituent on the phenyl group) and N-phenyliminodiacetic acids (which may or may not have a substituent on the phenyl group). (iii) Sulfur-containing compounds: The above-mentioned amines in which the nitrogen atom is replaced with a sulfur atom can generate active radicals by the same action, such as phenylthioacetic acid (which may or may not have a substituent on the phenyl group). (iv) Tin-containing compounds: Compounds in which the nitrogen atom of the above-mentioned amines is replaced with a tin atom can generate active radicals by the same action. (v) Sulfinates: capable of generating active radicals by oxidation. Specific examples include sodium arylsulfinates.

[0066] Among these, the image recording layer preferably contains a borate compound from the viewpoints of printing durability and color development. From the viewpoints of printing durability and color development, the borate compound is preferably a tetraarylborate compound or a monoalkyltriarylborate compound, and more preferably a tetraarylborate compound. The counter cation of the borate compound is not particularly limited, but is preferably an alkali metal ion or a tetraalkylammonium ion, and more preferably a sodium ion, a potassium ion, or a tetrabutylammonium ion.

[0067] A specific example of a preferred borate compound is sodium tetraphenylborate.

[0068] Preferred specific examples of the electron-donating polymerization initiator include, but are not limited to, B-1 to B-9. In the following chemical formulas, Ph represents a phenyl group, and Bu represents an n-butyl group.

[0069] [ka]

[0070] The electron-donating polymerization initiator may be added either alone or in combination of two or more. From the viewpoints of color development and suppression of fading over time, the content of the electron-donating polymerization initiator is preferably 0.01% by mass to 30% by mass, more preferably 0.05% by mass to 25% by mass, and even more preferably 0.1% by mass to 20% by mass, relative to the total mass of the image recording layer.

[0071] -Polymerizable compound- The image recording layer preferably contains a polymerizable compound. The polymerizable compound used in the present disclosure may be, for example, a radical polymerizable compound or a cationic polymerizable compound, but is preferably an addition polymerizable compound (ethylenically unsaturated compound) having at least one ethylenically unsaturated bond. The ethylenically unsaturated compound is preferably a compound having at least one terminal ethylenically unsaturated bond, and more preferably a compound having two or more terminal ethylenically unsaturated bonds. The polymerizable compound has a chemical form such as, for example, a monomer, a prepolymer, i.e., a dimer, a trimer, or an oligomer, or a mixture thereof.

[0072] Examples of the monomer include unsaturated carboxylic acids (e.g., acrylic acid, methacrylic acid, itaconic acid, crotonic acid, isocrotonic acid, maleic acid, etc.), their esters, and amides. Preferably, esters of unsaturated carboxylic acids and polyhydric alcohol compounds, and amides of unsaturated carboxylic acids and polyvalent amine compounds are used. In addition, addition reaction products of unsaturated carboxylic acid esters or amides having nucleophilic substituents such as hydroxyl groups, amino groups, and mercapto groups with monofunctional or polyfunctional isocyanates or epoxy groups, and dehydration condensation reaction products of monofunctional or polyfunctional carboxylic acids are also preferably used. In addition, addition reaction products of unsaturated carboxylic acid esters or amides having electrophilic substituents such as isocyanate groups and epoxy groups with monofunctional or polyfunctional alcohols, amines, and thiols, and substitution reaction products of unsaturated carboxylic acid esters or amides having eliminable substituents such as halogen atoms and tosyloxy groups with monofunctional or polyfunctional alcohols, amines, and thiols are also suitable. As another example, it is also possible to use a compound group in which the above unsaturated carboxylic acid is replaced with an unsaturated phosphonic acid, styrene, vinyl ether, or the like. These are described in JP-T-2006-508380, JP-A-2002-287344, JP-A-2008-256850, JP-A-2001-342222, JP-A-9-179296, JP-A-9-179297, JP-A-9-179298, JP-A-2004-294935, JP-A-2006-243493, JP-A-2002-275129, JP-A-2003-64130, JP-A-2003-280187, JP-A-10-333321, and the like.

[0073] Specific examples of monomers of esters of polyhydric alcohol compounds and unsaturated carboxylic acids include acrylic esters such as ethylene glycol diacrylate, 1,3-butanediol diacrylate, tetramethylene glycol diacrylate, propylene glycol diacrylate, trimethylolpropane triacrylate, hexanediol diacrylate, tetraethylene glycol diacrylate, pentaerythritol tetraacrylate, sorbitol triacrylate, isocyanuric acid ethylene oxide (EO) modified triacrylate, polyester acrylate oligomer, etc. Specific examples of methacrylic esters include tetramethylene glycol dimethacrylate, neopentyl glycol dimethacrylate, trimethylolpropane trimethacrylate, ethylene glycol dimethacrylate, pentaerythritol trimethacrylate, bis[p-(3-methacryloxy-2-hydroxypropoxy)phenyl]dimethylmethane, bis[p-(methacryloxyethoxy)phenyl]dimethylmethane, etc. Specific examples of amide monomers of polyamine compounds and unsaturated carboxylic acids include methylene bisacrylamide, methylene bismethacrylamide, 1,6-hexamethylene bisacrylamide, 1,6-hexamethylene bismethacrylamide, diethylenetriamine trisacrylamide, xylylene bisacrylamide, and xylylene bismethacrylamide.

[0074] Also suitable are urethane-based addition polymerizable compounds produced by an addition reaction between an isocyanate and a hydroxy group. Specific examples thereof include vinyl urethane compounds containing two or more polymerizable vinyl groups in one molecule, which are obtained by adding a vinyl monomer containing a hydroxy group represented by the following formula (M) to a polyisocyanate compound having two or more isocyanate groups in one molecule, as described in JP-B-48-41708. CH2=C(R M4 )COOCH2CH(R M5 )OH (M) In formula (M), R M4 and R M5 each independently represents a hydrogen atom or a methyl group.

[0075] In addition, urethane acrylates described in JP-A-51-37193, JP-B-2-32293, JP-B-2-16765, JP-A-2003-344997, and JP-A-2006-65210, JP-B-58-49860, JP-B-56-17654, JP-B-62-39417, and JP-B-62-39418 Also suitable are urethane compounds having an ethylene oxide skeleton described in JP-A-2000-250211 and JP-A-2007-94138, and urethane compounds having a hydrophilic group described in U.S. Pat. No. 7,153,632, JP-T-8-505958, JP-A-2007-293221 and JP-A-2007-293223.

[0076] Details of the method of use, such as the structure of the polymerizable compound, whether it is used alone or in combination, and the amount added, can be set arbitrarily. The content of the polymerizable compound is preferably from 5 to 75% by mass, more preferably from 10 to 70% by mass, and particularly preferably from 15 to 60% by mass, based on the total mass of the image recording layer.

[0077] -Binder polymer- The image recording layer preferably further contains a binder polymer. The binder polymer is preferably a (meth)acrylic resin, a polyvinyl acetal resin, or a polyurethane resin.

[0078] Among them, the binder polymer may suitably be a known binder polymer used in the image recording layer of a lithographic printing plate precursor. As an example, a binder polymer used in an on-press development type lithographic printing plate precursor (hereinafter also referred to as an on-press development binder polymer) will be described in detail. The binder polymer for on-press development is preferably a binder polymer having an alkylene oxide chain. The binder polymer having an alkylene oxide chain may have a poly(alkylene oxide) moiety in the main chain or in the side chain. In addition, the binder polymer may be a graft polymer having a poly(alkylene oxide) in the side chain, or a block copolymer of a block composed of a poly(alkylene oxide)-containing repeating unit and a block composed of a non-(alkylene oxide)-containing repeating unit. When the main chain has a poly(alkylene oxide) moiety, polyurethane resin is preferred. When the main chain has a poly(alkylene oxide) moiety in the side chain, examples of the polymer of the main chain include (meth)acrylic resin, polyvinyl acetal resin, polyurethane resin, polyurea resin, polyimide resin, polyamide resin, epoxy resin, polystyrene resin, novolac type phenolic resin, polyester resin, synthetic rubber, and natural rubber, and (meth)acrylic resin is particularly preferred.

[0079] Another preferred example of the binder polymer is a polymer compound (hereinafter also referred to as a star-shaped polymer compound) having a 6- to 10-functional polyfunctional thiol core, a polymer chain bonded to the core by a sulfide bond, and the polymer chain having a polymerizable group. For example, the compound described in JP-A-2012-148555 can be preferably used as the star-shaped polymer compound.

[0080] Examples of star-shaped polymer compounds include those having a polymerizable group such as an ethylenically unsaturated bond in the main chain or side chain, preferably in the side chain, for improving the film strength in the image area as described in JP-A-2008-195018. The polymerizable group forms a crosslink between polymer molecules, accelerating curing. As the polymerizable group, an ethylenically unsaturated group such as a (meth)acrylic group, a vinyl group, an allyl group, or a styryl group, or an epoxy group, etc. are preferred, and a (meth)acrylic group, a vinyl group, or a styryl group is more preferred from the viewpoint of polymerization reactivity, and a (meth)acrylic group is particularly preferred. These groups can be introduced into a polymer by a polymer reaction or copolymerization. For example, a reaction between a polymer having a carboxy group in a side chain and glycidyl methacrylate, or a reaction between a polymer having an epoxy group and an ethylenically unsaturated group-containing carboxylic acid such as methacrylic acid can be utilized. These groups may be used in combination.

[0081] The molecular weight of the binder polymer is preferably a weight average molecular weight (Mw) of 2,000 or more, more preferably 5,000 or more, and further preferably 10,000 to 300,000, as calculated as polystyrene by the GPC method.

[0082] If necessary, a hydrophilic polymer such as polyacrylic acid or polyvinyl alcohol described in JP-A-2008-195018 can be used in combination. Also, a lipophilic polymer and a hydrophilic polymer can be used in combination.

[0083] In the image recording layer used in the present disclosure, the binder polymer may be used alone or in combination of two or more kinds. The binder polymer can be contained in any amount in the image recording layer, but the content of the binder polymer is preferably 1% by mass to 90% by mass, and more preferably 5% by mass to 80% by mass, relative to the total mass of the image recording layer.

[0084] -Acid color former- The image recording layer preferably contains an acid color former (hereinafter, also simply referred to as "acid color former"). The term "acid color former" used in the present disclosure means a compound that has the property of developing color when heated in a state in which it accepts an electron-accepting compound (e.g., a proton of an acid, etc.). As the acid color former, in particular, a colorless compound having a partial skeleton such as lactone, lactam, sultone, spiropyran, ester, amide, etc., which rapidly opens or cleaves the partial skeleton when it comes into contact with an electron-accepting compound is preferred.

[0085] Examples of such acid color formers include 3,3-bis(4-dimethylaminophenyl)-6-dimethylaminophthalide (also called "crystal violet lactone"), 3,3-bis(4-dimethylaminophenyl)phthalide, 3-(4-dimethylaminophenyl)-3-(4-diethylamino-2-methylphenyl)-6-dimethylaminophthalide, 3-(4-dimethylaminophenyl)-3-(1,2-dimethylindol-3-yl)phthalide, 3-(4-dimethylaminophenyl)-3-(2-methylindol-3-yl)phthalide, and 3-(4-dimethylaminophenyl)-3-(2-methylindol-3-yl)phthalide. 3,3-bis(1,2-dimethylindol-3-yl)phthalide, 3,3-bis(1,2-dimethylindol-3-yl)-5-dimethylaminophthalide, 3,3-bis(1,2-dimethylindol-3-yl)-6-dimethylaminophthalide, 3,3-bis(9-ethylcarbazol-3-yl)-6-dimethylaminophthalide, 3,3-bis(2-phenylindol-3-yl)-6-dimethylaminophthalide, 3-(4-dimethylaminophenyl)-3-(1-methylpyrrol-3-yl)-6-dimethylaminophthalide,

[0086] 3,3-bis[1,1-bis(4-dimethylaminophenyl)ethylene-2-yl]-4,5,6,7-tetrachlorophthalide, 3,3-bis[1,1-bis(4-pyrrolidinophenyl)ethylene-2-yl]-4,5,6,7-tetrabromophthalide, 3,3-bis[1-(4-dimethylaminophenyl)-1-(4-methoxyphenyl)ethylene-2-yl]-4,5,6,7-tetrachlorophthalide, 3,3-bis[1-(4-pyrrolidinophenyl)-1-(4-methoxyphenyl)ethylene-2-yl]-4,5,6,7-tetrachlorophthalide, 3-[1,1-di(1-ethyl-2-methylindo phthalides such as 3-[1,1-di(1-ethyl-2-methylindol-3-yl)ethylene-2-yl]-3-(4-diethylaminophenyl)phthalide, 3-[1,1-di(1-ethyl-2-methylindol-3-yl)ethylene-2-yl]-3-(4-N-ethyl-N-phenylaminophenyl)phthalide, 3-(2-ethoxy-4-diethylaminophenyl)-3-(1-n-octyl-2-methylindol-3-yl)-phthalide, 3,3-bis(1-n-octyl-2-methylindol-3-yl)-phthalide, and 3-(2-methyl-4-diethylaminophenyl)-3-(1-n-octyl-2-methylindol-3-yl)-phthalide;

[0087] 4,4-Bis-dimethylaminobenzhydrin benzyl ether, N-halophenyl-leucoauramine, N-2,4,5-trichlorophenylleucoauramine, rhodamine-B-anilinolactam, rhodamine-(4-nitroanilino)lactam, rhodamine-B-(4-chloroanilino)lactam, 3,7-bis(diethylamino)-10-benzoylphenoxazine, benzoylleuco methylene blue, 4-nitrobenzoyl methylene blue,

[0088] 3,6-dimethoxyfluoran, 3-dimethylamino-7-methoxyfluoran, 3-diethylamino-6-methoxyfluoran, 3-diethylamino-7-methoxyfluoran, 3-diethylamino-7-chlorofluoran, 3-diethylamino-6-methyl-7-chlorofluoran, 3-diethylamino-6,7-dimethylfluoran, 3-N-cyclohexyl-Nn-butylamino-7-methylfluoran, 3-diethylamino-7-dibenzylaminofluoran, 3-diethylamino-7-octylaminofluoran, 3-diethylamino-7-di-n-hexylaminofluoran, 3-diethylamino-7-anilinofluoran, 3- Diethylamino-7-(2'-fluorophenylamino)fluoran, 3-diethylamino-7-(2'-chlorophenylamino)fluoran, 3-diethylamino-7-(3'-chlorophenylamino)fluoran, 3-diethylamino-7-(2',3'-dichlorophenylamino)fluoran, 3-diethylamino-7-(3'-trifluoromethylphenylamino)fluoran, 3-di-n-butylamino-7-(2'-fluorophenylamino)fluoran, 3-di-n-butylamino-7-(2'-chlorophenylamino)fluoran, 3-N-isopentyl-N-ethylamino-7-(2'-chlorophenylamino)fluoran,

[0089] 3-Nn-hexyl-N-ethylamino-7-(2'-chlorophenylamino)fluoran, 3-diethylamino-6-chloro-7-anilinofluoran, 3-di-n-butylamino-6-chloro-7-anilinofluoran, 3-diethylamino-6-methoxy-7-anilinofluoran, 3-di-n-butylamino-6-ethoxy-7-anilinofluoran, 3-pyrrolidino-6-methyl-7-anilinofluoran, 3-piperidino-6-methyl-7-anilinofluoran, 3-morpholino- 6-Methyl-7-anilinofluoran, 3-dimethylamino-6-methyl-7-anilinofluoran, 3-diethylamino-6-methyl-7-anilinofluoran, 3-di-n-butylamino-6-methyl-7-anilinofluoran, 3-di-n-pentylamino-6-methyl-7-anilinofluoran, 3-N-ethyl-N-methylamino-6-methyl-7-anilinofluoran, 3-Nn-propyl-N-methylamino-6-methyl-7-anilinofluoran, 3-Nn-propyl-N-ethyl N-butyl-N-methylamino-6-methyl-7-anilinofluoran, 3-N-butyl-N-ethylamino-6-methyl-7-anilinofluoran, 3-N-isobutyl-N-methylamino-6-methyl-7-anilinofluoran, 3-N-isobutyl-N-ethylamino-6-methyl-7-anilinofluoran, 3-N-isopentyl-N-ethylamino-6-methyl-7-anilinofluoran, 3-N-hexyl-N-methylamino amino-6-methyl-7-anilinofluoran, 3-N-cyclohexyl-N-ethylamino-6-methyl-7-anilinofluoran, 3-N-cyclohexyl-Nn-propylamino-6-methyl-7-anilinofluoran, 3-N-cyclohexyl-Nn-butylamino-6-methyl-7-anilinofluoran, 3-N-cyclohexyl-Nn-hexylamino-6-methyl-7-anilinofluoran, 3-N-cyclohexyl-Nn-octylamino-6-methyl-7-anilinofluoran,

[0090] 3-N-(2'-methoxyethyl)-N-methylamino-6-methyl-7-anilinofluoran, 3-N-(2'-methoxyethyl)-N-ethylamino-6-methyl-7-anilinofluoran, 3-N-(2'-methoxyethyl)-N-isobutylamino-6-methyl-7-anilinofluoran, 3-N-(2'-ethoxyethyl)-N-methylamino-6-methyl-7-anilinofluoran, 3-N-(2'-ethoxyethyl)-N-ethylamino-6-methyl-7 -Anilinofluoran, 3-N-(3'-methoxypropyl)-N-methylamino-6-methyl-7-anilinofluoran, 3-N-(3'-methoxypropyl)-N-ethylamino-6-methyl-7-anilinofluoran, 3-N-(3'-ethoxypropyl)-N-methylamino-6-methyl-7-anilinofluoran, 3-N-(3'-ethoxypropyl)-N-ethylamino-6-methyl-7-anilinofluoran, 3-N-(3'-ethoxypropyl)-N-ethylamino-6-methyl-7-anilinofluoran, 3-N-(2'-tetrahydrofurfuryl)- N-ethylamino-6-methyl-7-anilinofluoran, 3-N-(4'-methylphenyl)-N-ethylamino-6-methyl-7-anilinofluoran, 3-diethylamino-6-ethyl-7-anilinofluoran, 3-diethylamino-6-methyl-7-(3'-methylphenylamino)fluoran, 3-diethylamino-6-methyl-7-(2',6'-dimethylphenylamino)fluoran, 3-di-n-butylamino-6-methyl-7-(2',6'-dimethylphenylamino)fluoran, fluorans such as 3-di-n-butylamino-7-(2',6'-dimethylphenylamino)fluoran, 3-di-n-butylamino-7-(2',6'-dimethylphenylamino)fluoran, 2,2-bis[4'-(3-N-cyclohexyl-N-methylamino-6-methylfluoran)-7-ylaminophenyl]propane, 3-[4'-(4-phenylaminophenyl)aminophenyl]amino-6-methyl-7-chlorofluoran, and 3-[4'-(dimethylaminophenyl)]amino-5,7-dimethylfluoran;

[0091] 3-(2-methyl-4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-azaphthalide, 3-(2-n-propoxycarbonylamino-4-di-n-propylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-azaphthalide, 3-(2-methylamino-4-di-n-propylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-azaphthalide, 3-(2-methyl-4-di-n-hexylaminophenyl)-3-(1-n-octyl 3-(2-ethoxy-4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-azaphthalide, 3,3-bis(2-ethoxy-4-diethylaminophenyl)-4-azaphthalide, 3,3-bis(1-n-octyl-2-methylindol-3-yl)-4-azaphthalide, 3-(2-ethoxy-4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-azaphthalide, 3-(2-ethoxy-4-diethylaminophenyl)-3-(1-octyl-2-methylindol-3-yl)-4 or 7-azaphthalide, 3-( 2-ethoxy-4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)-4 or 7-azaphthalide, 3-(2-hexyloxy-4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)-4 or 7-azaphthalide, 3-(2-ethoxy-4-diethylaminophenyl)-3-(1-ethyl-2-phenylindol-3-yl)-4 or 7-azaphthalide, 3-(2-butoxy-4-diethylaminophenyl)-3-(1-ethyl-2-phenylindol-3 -yl)-4 or 7-azaphthalide 3-methyl-spiro-dinaphthopyran, 3-ethyl-spiro-dinaphthopyran, 3-phenyl-spiro-dinaphthopyran, 3-benzyl-spiro-dinaphthopyran, 3-methyl-naphtho-(3-methoxybenzo)spiropyran, 3-propyl-spiro-dibenzopyran-3,6-bis(dimethylamino)fluorene-9-spiro-3'-(6'-dimethylamino)phthalide, 3,6-bis(diethylamino)fluorene-9-spiro-3'-(6'-dimethylamino)phthalide and other phthalides;

[0092] Other examples include 2'-anilino-6'-(N-ethyl-N-isopentyl)amino-3'-methylspiro[isobenzofuran-1(3H),9'-(9H)xanthene-3-one, 2'-anilino-6'-(N-ethyl-N-(4-methylphenyl))amino-3'-methylspiro[isobenzofuran-1(3H),9'-(9H)xanthene]-3-one, 3'-N,N-dibenzylamino-6'-N,N-diethylaminospiro[isobenzofuran-1(3H),9'-(9H)xanthene]-3-one, and 2'-(N-methyl-N-phenyl)amino-6'-(N-ethyl-N-(4-methylphenyl))aminospiro[isobenzofuran-1(3H),9'-(9H)xanthene]-3-one.

[0093] Among these, from the viewpoint of color development, the acid color former used in the present disclosure is preferably at least one compound selected from the group consisting of spiropyran compounds, spirooxazine compounds, spirolactone compounds, and spirolactam compounds. From the viewpoint of visibility, the hue of the dye after color development is preferably green, blue or black.

[0094] Commercially available products can be used as acid colorants, including ETAC, RED500, RED520, CVL, S-205, BLACK305, BLACK400, BLACK100, BLACK500, H-7001, GREEN300, NIRBLACK78, BLUE220, H-3035, BLUE203, ATP, H-1046, H-2114 (all manufactured by Fukui Yamada Chemical Industry Co., Ltd.), ORANGE-DCF, and Vermilio. Examples of such dyes include n-DCF, PINK-DCF, RED-DCF, BLMB, CVL, GREEN-DCF, TH-107 (all manufactured by Hodogaya Chemical Co., Ltd.), ODB, ODB-2, ODB-4, ODB-250, ODB-BlackXV, Blue-63, Blue-502, GN-169, GN-2, Green-118, Red-40, Red-8 (all manufactured by Yamamoto Chemical Industry Co., Ltd.), and crystal violet lactone (manufactured by Tokyo Kaseihin Kogyo Co., Ltd.). Among these commercially available products, ETAC, S-205, BLACK305, BLACK400, BLACK100, BLACK500, H-7001, GREEN300, NIRBLACK78, H-3035, ATP, H-1046, H-2114, GREEN-DCF, Blue-63, GN-169, and crystal violet lactone are preferred because the films formed have good visible light absorptance.

[0095] These acid color formers may be used alone or in combination of two or more kinds. The content of the acid color former is preferably from 0.5% by mass to 10% by mass, and more preferably from 1% by mass to 5% by mass, based on the total mass of the image recording layer.

[0096] - Chain transfer agent - The image recording layer used in the present disclosure may contain a chain transfer agent. The chain transfer agent contributes to improving the printing durability of the lithographic printing plate. The chain transfer agent is preferably a thiol compound, more preferably a thiol having 7 or more carbon atoms from the viewpoint of boiling point (difficulty of volatilization), and further preferably a compound having a mercapto group on an aromatic ring (aromatic thiol compound).The thiol compound is preferably a monofunctional thiol compound.

[0097] Specific examples of the chain transfer agent include the following compounds.

[0098] [ka]

[0099] [ka]

[0100] [ka]

[0101] [ka]

[0102] The chain transfer agent may be added alone or in combination of two or more kinds. The content of the chain transfer agent is preferably from 0.01% by mass to 50% by mass, more preferably from 0.05% by mass to 40% by mass, and even more preferably from 0.1% by mass to 30% by mass, based on the total mass of the image recording layer.

[0103] -Low molecular hydrophilic compounds- The image recording layer may contain a low molecular weight hydrophilic compound in order to improve on-press developability while suppressing deterioration of printing durability. The low molecular weight hydrophilic compound is preferably a compound having a molecular weight of less than 1,000, more preferably a compound having a molecular weight of less than 800, and even more preferably a compound having a molecular weight of less than 500. Examples of low molecular weight hydrophilic compounds include water-soluble organic compounds such as glycols and their ether or ester derivatives, such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, and tripropylene glycol; polyols, such as glycerin, pentaerythritol, and tris(2-hydroxyethyl)isocyanurate; organic amines and their salts, such as triethanolamine, diethanolamine, and monoethanolamine; organic sulfonic acids and their salts, such as alkylsulfonic acid, toluenesulfonic acid, and benzenesulfonic acid; organic sulfamic acids and their salts, such as alkylsulfamic acid; organic sulfuric acids and their salts, such as alkylsulfuric acid and alkyl ether sulfuric acid; organic phosphonic acids and their salts, such as phenylphosphonic acid; organic carboxylic acids and their salts, such as tartaric acid, oxalic acid, citric acid, malic acid, lactic acid, gluconic acid, and amino acids; and betaines.

[0104] As the low molecular weight hydrophilic compound, it is preferable to contain at least one selected from polyols, organic sulfates, organic sulfonates, and betaines.

[0105] Specific examples of organic sulfonates include alkyl sulfonates such as sodium n-butyl sulfonate, sodium n-hexyl sulfonate, sodium 2-ethylhexyl sulfonate, sodium cyclohexyl sulfonate, and sodium n-octyl sulfonate; alkyl sulfonates containing an ethylene oxide chain such as sodium 5,8,11-trioxapentadecane-1-sulfonate, sodium 5,8,11-trioxaheptadecane-1-sulfonate, sodium 13-ethyl-5,8,11-trioxaheptadecane-1-sulfonate, and sodium 5,8,11,14-tetraoxatetracosane-1-sulfonate. arylsulfonates such as sodium benzenesulfonate, sodium p-toluenesulfonate, sodium p-hydroxybenzenesulfonate, sodium p-styrenesulfonate, sodium isophthalate dimethyl-5-sulfonate, sodium 1-naphthylsulfonate, sodium 4-hydroxynaphthylsulfonate, disodium 1,5-naphthalenedisulfonate, and trisodium 1,3,6-naphthalenetrisulfonate; and the compounds described in paragraphs 0026 to 0031 of JP-A No. 2007-276454 and paragraphs 0020 to 0047 of JP-A No. 2009-154525. The salt may be a potassium salt or a lithium salt.

[0106] The organic sulfates include sulfates of alkyl, alkenyl, alkynyl, aryl, or heterocyclic monoether of polyethylene oxide. The number of ethylene oxide units is preferably 1 to 4, and the salt is preferably a sodium salt, a potassium salt, or a lithium salt. Specific examples include the compounds described in paragraphs 0034 to 0038 of JP-A-2007-276454.

[0107] As the betaines, compounds in which the number of carbon atoms in the hydrocarbon substituent on the nitrogen atom is 1 to 5 are preferable, and specific examples include trimethylammonium acetate, dimethylpropylammonium acetate, 3-hydroxy-4-trimethylammoniobutyrate, 4-(1-pyridinio)butyrate, 1-hydroxyethyl-1-imidazolioacetate, trimethylammonium methanesulfonate, dimethylpropylammonium methanesulfonate, 3-trimethylammonio-1-propanesulfonate, and 3-(1-pyridinio)-1-propanesulfonate.

[0108] Since the structure of the hydrophobic portion of a low molecular weight hydrophilic compound is small and it has almost no surfactant effect, the dampening water does not penetrate into the exposed area (image area) of the image recording layer and reduce the hydrophobicity or film strength of the image area, and the ink receptivity and printing durability of the image recording layer can be maintained at a good level.

[0109] The content of the low molecular weight hydrophilic compound is preferably 0.5% by mass to 20% by mass, more preferably 1% by mass to 15% by mass, and even more preferably 2% by mass to 10% by mass, based on the total mass of the image recording layer. Within this range, good on-press developability and printing durability can be obtained. The low molecular weight hydrophilic compound may be used alone or in combination of two or more kinds.

[0110] -Oil sensitizer- In order to improve ink receptivity, the image recording layer may contain an oil sensitizer such as a phosphonium compound, a nitrogen-containing low molecular weight compound, an ammonium group-containing polymer, etc. In particular, when an inorganic layer compound is contained in the protective layer, these compounds function as a surface coating agent for the inorganic layer compound, and can suppress a decrease in ink receptivity during printing caused by the inorganic layer compound. As the oil sensitizer, it is preferable to use a phosphonium compound, a nitrogen-containing low molecular weight compound, and an ammonium group-containing polymer in combination, and it is more preferable to use a phosphonium compound, a quaternary ammonium salt, and an ammonium group-containing polymer in combination.

[0111] Examples of the phosphonium compound include those described in JP-A-2006-297907 and JP-A-2007-50660.Specific examples include tetrabutylphosphonium iodide, butyltriphenylphosphonium bromide, tetraphenylphosphonium bromide, 1,4-bis(triphenylphosphonio)butane=di(hexafluorophosphate), 1,7-bis(triphenylphosphonio)heptane=sulfate, and 1,9-bis(triphenylphosphonio)nonane=naphthalene-2,7-disulfonate.

[0112] Examples of the nitrogen-containing low molecular weight compound include amine salts and quaternary ammonium salts. Examples of the nitrogen-containing low molecular weight compound include imidazolinium salts, benzimidazolinium salts, pyridinium salts, and quinolinium salts. Among them, quaternary ammonium salts and pyridinium salts are preferred. Specific examples include tetramethylammonium hexafluorophosphate, tetrabutylammonium hexafluorophosphate, dodecyltrimethylammonium p-toluenesulfonate, benzyltriethylammonium hexafluorophosphate, benzyldimethyloctylammonium hexafluorophosphate, benzyldimethyldodecylammonium hexafluorophosphate, and the compounds described in paragraphs 0021 to 0037 of JP-A-2008-284858 and paragraphs 0030 to 0057 of JP-A-2009-90645.

[0113] The ammonium group-containing polymer may have an ammonium group in its structure, and is preferably a polymer containing 5 mol % to 80 mol % of a (meth)acrylate having an ammonium group in a side chain as a copolymerization component. Specific examples include the polymers described in paragraphs 0089 to 0105 of JP-A-2009-208458.

[0114] The ammonium salt-containing polymer preferably has a reduced specific viscosity (unit: ml / g) value determined according to the measurement method described in JP 2009-208458 A in the range of 5 to 120, more preferably 10 to 110, and particularly preferably 15 to 100. When the reduced specific viscosity is converted into a weight average molecular weight (Mw), it is preferably 10,000 to 150,0000, more preferably 17,000 to 140,000, and particularly preferably 20,000 to 130,000.

[0115] Specific examples of the ammonium group-containing polymer are shown below. (1) 2-(trimethylammonio)ethyl methacrylate = p-toluenesulfonate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 10 / 90, Mw 45,000) (2) 2-(trimethylammonio)ethyl methacrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 60,000) (3) 2-(ethyldimethylammonio)ethyl methacrylate = p-toluenesulfonate / hexyl methacrylate copolymer (molar ratio 30 / 70, Mw 45,000) (4) 2-(trimethylammonio)ethyl methacrylate = hexafluorophosphate / 2-ethylhexyl methacrylate copolymer (molar ratio 20 / 80, Mw 60,000) (5) 2-(trimethylammonio)ethyl methacrylate = methyl sulfate / hexyl methacrylate copolymer (molar ratio 40 / 60, Mw 70,000) (6) 2-(butyldimethylammonio)ethyl methacrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 25 / 75, Mw 65,000) (7) 2-(butyldimethylammonio)ethyl acrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 65,000) (8) 2-(butyldimethylammonio)ethyl methacrylate = 13-ethyl-5,8,11-trioxa-1-heptadecanesulfonate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 75,000) (9) 2-(butyldimethylammonio)ethyl methacrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate / 2-hydroxy-3-methacryloyloxypropyl methacrylate copolymer (molar ratio 15 / 80 / 5, Mw 65,000)

[0116] The content of the oil sensitizer is preferably from 0.01% by mass to 30.0% by mass, more preferably from 0.1% by mass to 15.0% by mass, and even more preferably from 1% by mass to 10% by mass, based on the total mass of the image recording layer.

[0117] -Other ingredients- The image recording layer may contain other components such as surfactants, polymerization inhibitors, higher fatty acid derivatives, plasticizers, inorganic particles, inorganic layer compounds, etc. For details, see paragraphs 0114 to 0159 of JP2008-284817A.

[0118] - Formation of image recording layer - The image recording layer in the lithographic printing plate precursor according to the present disclosure can be formed, for example, as described in paragraphs

[0142] to

[0143] of JP-A No. 2008-195018 by dispersing or dissolving the necessary components described above in a known solvent to prepare a coating liquid, applying the coating liquid onto a support by a known method such as bar coater coating, and drying. The coating amount (solid content) of the image recording layer after coating and drying varies depending on the application, but is generally 0.3 g / m 2 ~3.0g / m 2 In this range, good sensitivity and good film properties of the image recording layer can be obtained. As the solvent, a known solvent can be used.Specific examples of the solvent include water, acetone, methyl ethyl ketone (2-butanone), cyclohexane, ethyl acetate, ethylene dichloride, tetrahydrofuran, toluene, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, acetylacetone, cyclohexanone, diacetone alcohol, ethylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether acetate, 1-methoxy-2-propanol, 3-methoxy-1-propanol, methoxymethoxyethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, 3-methoxypropyl acetate, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, methyl lactate, and ethyl lactate. The solvent may be used alone or in combination of two or more kinds. The solid content concentration in the coating liquid is preferably about 1 to 50 mass %. The coating amount (solid content) of the image recording layer after coating and drying varies depending on the application, but is preferably about 0.3 to 3.0 g / m2 from the viewpoint of obtaining good sensitivity and good film properties of the image recording layer.

[0119] <Support> The support in the lithographic printing plate precursor according to the present disclosure can be appropriately selected from known hydrophilic supports for lithographic printing plate precursors. The support is preferably a hydrophilic support. The hydrophilic support is preferably an aluminum plate that has been roughened and anodized by a known method. The aluminum plate may further be subjected to an appropriate selection of treatments, such as enlarging or sealing micropores in the anodized film as described in JP-A-2001-253181 and JP-A-2001-322365, surface hydrophilization treatment with an alkali metal silicate as described in U.S. Pat. Nos. 2,714,066, 3,181,461, 3,280,734, and 3,902,734, or surface hydrophilization treatment with polyvinyl phosphonic acid as described in U.S. Pat. Nos. 3,276,868, 4,153,461, and 4,689,272. The support preferably has a center line average roughness of 0.10 μm to 1.2 μm.

[0120] If necessary, the support may have a backcoat layer containing an organic polymer compound described in JP-A-5-45885 or a silicon alkoxy compound described in JP-A-6-35174 on the side opposite the image recording layer.

[0121] <Undercoat layer> The lithographic printing plate precursor according to the present disclosure preferably has an undercoat layer (sometimes called an intermediate layer) between the image recording layer and the support. The undercoat layer strengthens the adhesion between the support and the image recording layer in the exposed area, and facilitates peeling of the image recording layer from the support in the unexposed area, thereby contributing to improving developability without impairing printing durability. In addition, in the case of infrared laser exposure, the undercoat layer functions as a heat insulating layer, thereby preventing the heat generated by exposure from diffusing to the support and reducing sensitivity.

[0122] The compound used in the undercoat layer may be a polymer having an adsorptive group and a hydrophilic group that can be adsorbed to the support surface. In order to improve adhesion with the image recording layer, a polymer having an adsorptive group and a hydrophilic group and further having a crosslinkable group is preferred. The compound used in the undercoat layer may be a low molecular weight compound or a polymer. The compound used in the undercoat layer may be a mixture of two or more kinds, if necessary.

[0123] When the compound used in the undercoat layer is a polymer, it is preferably a copolymer of a monomer having an adsorptive group, a monomer having a hydrophilic group, and a monomer having a crosslinkable group. The adsorptive group capable of being adsorbed to the surface of the support is preferably a phenolic hydroxy group, a carboxy group, -PO3H2, -OPO3H2, -CONHSO2-, -SO2NHSO2-, or -COCH2COCH3. The hydrophilic group is preferably a sulfo group or a salt thereof, or a salt of a carboxy group. The crosslinkable group is preferably an acryl group, a methacryl group, an acrylamide group, a methacrylamide group, or an allyl group. The polymer may have a crosslinkable group introduced by salt formation between a polar substituent of the polymer and a compound having an ethylenically unsaturated bond and a substituent having an opposite charge to the polar substituent, or may further be copolymerized with a monomer other than the above-mentioned monomers, preferably a hydrophilic monomer.

[0124] Specifically, preferred examples include a silane coupling agent having an addition-polymerizable ethylenic double bond reactive group described in JP-A-10-282679 and a phosphorus compound having an ethylenic double bond reactive group described in JP-A-2-304441. Also preferred are low-molecular or high-molecular compounds having a crosslinkable group (preferably an ethylenic unsaturated bond group), a functional group that interacts with the support surface, and a hydrophilic group described in JP-A-2005-238816, JP-A-2005-125749, JP-A-2006-239867, and JP-A-2006-215263. More preferred examples include polymers having an adsorptive group, a hydrophilic group and a crosslinkable group capable of being adsorbed onto the surface of a support, as described in JP-A Nos. 2005-125749 and 2006-188038.

[0125] The content of the ethylenically unsaturated bond group in the polymer used in the undercoat layer is preferably from 0.1 mmol to 10.0 mmol, and more preferably from 0.2 mmol to 5.5 mmol, per 1 g of the polymer. The weight average molecular weight (Mw) of the polymer used in the undercoat layer is preferably 5,000 or more, and more preferably from 10,000 to 300,000.

[0126] In addition to the above-mentioned compounds for the undercoat layer, the undercoat layer may contain a chelating agent, a secondary or tertiary amine, a polymerization inhibitor, a compound having an amino group or a functional group having polymerization inhibitory ability and a group that interacts with the support surface (e.g., 1,4-diazabicyclo[2.2.2]octane (DABCO), 2,3,5,6-tetrahydroxy-p-quinone, chloranil, sulfophthalic acid, hydroxyethylethylenediaminetriacetic acid, dihydroxyethylethylenediaminediacetic acid, hydroxyethyliminodiacetic acid, etc.) to prevent contamination over time.

[0127] The undercoat layer is applied by a known method. The coating amount (solid content) of the undercoat layer is 0.1 mg / m 2 ~100mg / m 2 is preferred, and 1 mg / m 2 ~30mg / m 2 is more preferred.

[0128] <Protective layer> The lithographic printing plate precursor according to the present disclosure preferably has a protective layer (sometimes called an overcoat layer) on the image recording layer. The protective layer has a function of suppressing image formation inhibiting reactions by blocking oxygen, as well as a function of preventing the image recording layer from being scratched and from being ablated during exposure to a high-intensity laser.

[0129] A protective layer having such characteristics is described, for example, in U.S. Pat. No. 3,458,311 and Japanese Patent Publication No. 55-49729. As the low oxygen permeability polymer used in the protective layer, either a water-soluble polymer or a water-insoluble polymer can be appropriately selected and used, and two or more types can be mixed and used as necessary. Specific examples include polyvinyl alcohol, modified polyvinyl alcohol, polyvinylpyrrolidone, water-soluble cellulose derivatives, poly(meth)acrylonitrile, etc. The modified polyvinyl alcohol is preferably an acid-modified polyvinyl alcohol having a carboxy group or a sulfo group, specifically, the modified polyvinyl alcohols described in JP-A-2005-250216 and JP-A-2006-259137.

[0130] The protective layer preferably contains an inorganic layered compound to improve the oxygen barrier properties. The inorganic layered compound is a thin, tabular particle, and examples thereof include mica groups such as natural mica and synthetic mica, talc represented by the formula: 3MgO·4SiO·H2O, taeniolite, montmorillonite, saponite, hectorite, zirconium phosphate, and the like. The inorganic layered compound preferably used is a mica compound. Examples of the mica compound include those represented by the formula: A(B,C) 2-5 D4O 10 Examples of mica include natural mica and synthetic mica represented by the formula (OH,F,O)2 (wherein A is K, Na, or Ca, B and C are Fe(II), Fe(III), Mn, Al, Mg, or V, and D is Si or Al).

[0131] In the mica group, natural micas include muscovite, sodalite, phlogopite, biotite and lepidolite. Synthetic micas include fluorphlogopite KMg3(AlSi3O 10 )F2, potassium tetrasilicic mica KMg 2.5 SiO 10 )F2 and other non-swelling micas, and Na tetrasilicic mica NaMg 2.5 (SiO 10 )F2, Na or Li taeniolite (Na,Li)Mg2Li(SiO 10 ) F2, Na or Li hectorite of the montmorillonite series (Na, Li) 1 / 8 Mg 2 / 5 Li 1 / 8 (SiO 10 Examples of suitable micas include swellable micas such as )F2. Synthetic smectite is also useful.

[0132] Among the above mica compounds, fluorine-based swellable mica is particularly useful. That is, swellable synthetic mica has a layered structure consisting of unit crystal lattice layers with a thickness of about 10 Å to 15 Å (1 Å = 0.1 nm), and the metal atom substitution within the lattice is significantly larger than that of other clay minerals. As a result, the lattice layers have a positive charge deficiency, and to compensate for this, Li is inserted between the layers. + , Na + , Ca 2+ , Mg 2+ The cations present between these layers are called exchangeable cations and can be exchanged with various other cations. In particular, the cations present between the layers are Li + , Na + In the case of , the bond between the layered crystal lattices is weak due to the small ionic radius, and it swells greatly in water. When shear is applied in this state, it easily cleaves and forms a stable sol in water. Swellable synthetic mica has a strong tendency in this case, and is particularly preferred.

[0133] As for the shape of the mica compound, from the viewpoint of diffusion control, the thinner the thickness, the better, and the larger the planar size, the better, as long as it does not impede the smoothness of the coating surface or the transmittance of actinic rays. Therefore, the aspect ratio is preferably 20 or more, more preferably 100 or more, and particularly preferably 200 or more. The aspect ratio is the ratio of the major axis to the thickness of the particle, and can be measured, for example, from a projection of the particle in a microscopic photograph. The larger the aspect ratio, the greater the effect obtained.

[0134] The particle size of the mica compound is preferably 0.3 μm to 20 μm, more preferably 0.5 μm to 10 μm, and particularly preferably 1 μm to 5 μm in terms of average major axis. The average thickness of the particles is preferably 0.1 μm or less, more preferably 0.05 μm or less, and particularly preferably 0.01 μm or less. Specifically, for example, in the case of swellable synthetic mica, which is a representative compound, the preferred embodiment has a thickness of about 1 nm to 50 nm and a surface size (major axis) of about 1 μm to 20 μm.

[0135] The content of the inorganic layered compound is preferably 1% by mass to 60% by mass, more preferably 3% by mass to 50% by mass, based on the total solid content of the protective layer. Even when a plurality of inorganic layered compounds are used in combination, the total amount of the inorganic layered compounds is preferably within the above content. Within the above range, oxygen barrier properties are improved and good sensitivity is obtained. Also, deterioration of ink receptivity can be prevented.

[0136] The protective layer may contain known additives such as a plasticizer for imparting flexibility, a surfactant for improving coatability, inorganic particles for controlling surface slippage, etc. Furthermore, the protective layer may contain an oil sensitizer as described in the image recording layer.

[0137] The protective layer is applied by a known method. The coating amount (solid content) of the protective layer is 0.01 g / m 2 ~10g / m 2 is preferred, and 0.02 g / m 2 ~3g / m 2 More preferably, 0.02 g / m 2 ~1g / m 2 is particularly preferred.

[0138] (Method of making a lithographic printing plate and method of lithographic printing) A lithographic printing plate can be prepared by imagewise exposing the lithographic printing plate precursor according to the present disclosure and then subjecting it to a development treatment. The method for producing a lithographic printing plate according to the present disclosure preferably includes a step of exposing the lithographic printing plate precursor according to the present disclosure to light in an imagewise manner (hereinafter also referred to as an "exposure step"), and a step of removing the image recording layer in non-image areas on a printing press by supplying at least one selected from the group consisting of printing ink and fountain solution (hereinafter also referred to as an "on-press development step"). The lithographic printing method according to the present disclosure preferably includes a step of exposing the lithographic printing plate precursor according to the present disclosure in an imagewise manner (exposure step), a step of supplying at least one selected from the group consisting of printing ink and fountain solution to remove the image recording layer in non-image areas on the printing press to prepare a lithographic printing plate (on-press development step), and a step of printing with the obtained lithographic printing plate (printing step). Hereinafter, preferred aspects of each step of the method for producing a lithographic printing plate according to the present disclosure and the lithographic printing method according to the present disclosure will be described in order. Note that the lithographic printing plate precursor according to the present disclosure can also be developed with a developer. The exposure step and on-press development step in the method for preparing a lithographic printing plate will be described below, but the exposure step in the method for preparing a lithographic printing plate according to the present disclosure is the same as the exposure step in the lithographic printing method according to the present disclosure, and the on-press development step in the method for preparing a lithographic printing plate according to the present disclosure is the same as the on-press development step in the lithographic printing method according to the present disclosure.

[0139] <Exposure process> The method for producing a lithographic printing plate according to the present disclosure preferably includes an exposure step of imagewise exposing the lithographic printing plate precursor according to the present disclosure to form an exposed area and an unexposed area. The lithographic printing plate precursor according to the present disclosure is preferably imagewise exposed by laser exposure through a transparent original having a line image, a halftone dot image, or the like, or by laser light scanning based on digital data. The wavelength of the light source is preferably 750 nm to 1,400 nm. As a light source with a wavelength of 750 nm to 1,400 nm, a solid-state laser or a semiconductor laser that emits infrared rays is suitable. With regard to the infrared laser, the output is preferably 100 mW or more, the exposure time per pixel is preferably 20 microseconds or less, and the amount of irradiation energy is preferably 10 mJ / cm. 2 ~300mJ / cm 2 It is preferable to use a multi-beam laser device in order to shorten the exposure time. The exposure mechanism may be any of an internal drum type, an external drum type, a flatbed type, and the like. Image exposure can be carried out by a conventional method using a plate setter, etc. In the case of on-press development, the lithographic printing plate precursor may be mounted on a printing press and then image exposure may be carried out on the printing press.

[0140] <On-press development process> The method for producing a lithographic printing plate according to the present disclosure preferably includes an on-press development step of supplying at least one selected from the group consisting of printing ink and fountain solution to remove the image recording layer in non-image areas on the printing press. The on-press development method will be described below.

[0141] [On-press development method] In the on-press development method, it is preferable that an oil-based ink and an aqueous component are supplied to the image-exposed lithographic printing plate precursor on a printing press, and the image recording layer in the non-image areas is removed to prepare a lithographic printing plate. That is, after image exposure, the lithographic printing plate precursor is mounted on a printing press as it is without any development treatment, or the lithographic printing plate precursor is mounted on a printing press and then image exposure is performed on the printing press, and then an oil-based ink and an aqueous component are supplied to print. In the early stage of printing, the uncured image recording layer is dissolved or dispersed by either or both of the supplied oil-based ink and aqueous component in the non-image area and removed, exposing a hydrophilic surface in that area. On the other hand, in the exposed area, the image recording layer cured by exposure forms an oil-based ink receptive area having an oleophilic surface. The first thing supplied to the plate surface may be an oil-based ink or an aqueous component, but it is preferable to supply an oil-based ink first in order to prevent the aqueous component from being contaminated by the component of the image recording layer that has been removed. In this way, the lithographic printing plate precursor is developed on the press and used as it is for printing a large number of sheets. As the oil-based ink and aqueous component, printing ink and fountain solution for normal lithographic printing are preferably used.

[0142] As the laser for imagewise exposing the lithographic printing plate precursor according to the present disclosure, the wavelength of the light source is preferably 300 nm to 450 nm or 750 nm to 1,400 nm. In the case of a light source having a wavelength of 300 nm to 450 nm, a lithographic printing plate precursor containing a sensitizing dye having an absorption maximum in this wavelength region in an image recording layer is preferably used, and as the light source having a wavelength of 750 nm to 1,400 nm, the above-mentioned light sources are preferably used. As the light source having a wavelength of 300 nm to 450 nm, a semiconductor laser is suitable.

[0143] <Developer development process> The method for producing a lithographic printing plate according to the present disclosure may be a method including a step of exposing the lithographic printing plate precursor according to the present disclosure to light in an imagewise manner, and a step of removing the image recording layer in the non-image area using a developer to produce a lithographic printing plate (also referred to as a "developer development step"). In addition, the lithographic printing method according to the present disclosure may be a method including the steps of exposing the lithographic printing plate precursor according to the present disclosure to light in an imagewise manner, removing the image recording layer in the non-image areas with a developer to prepare a lithographic printing plate, and printing with the obtained lithographic printing plate. As the developer, a known developer can be used. The pH of the developer is not particularly limited and may be a strong alkaline developer, but preferred examples of the developer have a pH of 2 to 11. Preferred examples of the developer having a pH of 2 to 11 include developers containing at least one of a surfactant and a water-soluble polymer compound. In the development process using a strong alkaline developer, the protective layer is removed in a pre-washing step, followed by alkaline development, the alkali is removed in a post-washing step, a gum solution treatment is performed, and then drying is performed in a drying step. In addition, when using the above-mentioned developer containing a surfactant or a water-soluble polymer compound, development and gum solution treatment can be performed simultaneously. Therefore, a post-rinsing step is not particularly required, and development and gum solution treatment can be performed with one solution, followed by a drying step. Furthermore, removal of the protective layer can be performed simultaneously with development and gum solution treatment, so a pre-rinsing step is not particularly required. After development, it is preferable to remove excess developer using a squeeze roller or the like, and then perform drying.

[0144] <Printing process> The lithographic printing method according to the present disclosure includes a printing step of supplying printing ink to a lithographic printing plate to print a recording medium. The printing ink is not particularly limited, and various known inks can be used as desired. Preferred examples of the printing ink include oil-based inks and ultraviolet-curable inks (UV inks). In the printing process, dampening water may be supplied as necessary. The printing step may be carried out consecutively to the on-press development step or the developer development step without stopping the printing press. The recording medium is not particularly limited, and any known recording medium can be used as desired.

[0145] In the method for preparing a lithographic printing plate from a lithographic printing plate precursor according to the present disclosure and the lithographic printing method according to the present disclosure, the entire surface of the lithographic printing plate precursor may be heated as necessary before exposure, during exposure, or between exposure and development. Such heating promotes the image formation reaction in the image recording layer, and can provide advantages such as improved sensitivity and printing durability and stabilization of sensitivity. Heating before development is preferably performed under mild conditions of 150° C. or less. In the above embodiment, problems such as hardening of non-image areas can be prevented. Heating after development is preferably performed under very strong conditions, preferably in the range of 100° C. to 500° C. In the above range, sufficient image strengthening effect can be obtained and problems such as deterioration of the support and thermal decomposition of the image area can be suppressed. EXAMPLES

[0146] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited thereto. In the present examples, "%" and "parts" mean "mass%" and "mass parts", respectively, unless otherwise specified. In the polymer compounds, unless otherwise specified, the molecular weight is the weight average molecular weight (Mw), and the ratio of the constituent repeating units is the molar percentage. The weight average molecular weight (Mw) is a value measured as a polystyrene equivalent value by gel permeation chromatography (GPC). The average particle size means the volume average particle size, unless otherwise specified.

[0147] <Synthesis of particle p-1> 270 parts of 1-methoxy-2-propanol, 9.0 parts of compound A-3, 18.0 parts of compound B-1, and 3.0 parts of compound C-1 (n=90) were added to a three-neck flask, stirred under a nitrogen atmosphere, and heated to 70°C. Next, 0.3g of dimethyl 2,2'-azobis(2-methylpropionate) was added, and the mixture was heated and stirred at 70°C for 4 hours. 0.10 parts of dimethyl 2,2'-azobis(2-methylpropionate) was added, heated to 90°C, and reacted for another 4 hours. The reaction liquid was allowed to cool to room temperature (25° C.) to obtain a dispersion liquid of particles p-1 (solid content 10%). The average particle size of particles p-1 was 189 nm.

[0148] <Synthesis of particle p-2> 113 parts of distilled water, 15.0 parts of compound A-4, 4.0 parts of compound B-2, and 1.0 parts of compound C-2 were added to a three-neck flask, and the mixture was heated to 70°C under a nitrogen atmosphere. Next, 0.2 parts of potassium persulfate (KPS) was added, and the mixture was heated and stirred for 3 hours, and then heated to 95°C and reacted for 4 hours. The reaction liquid was allowed to cool to room temperature (25°C), and a dispersion of particles p-2 (solid content 15%) was obtained. The average particle size of particles p-2 was 146 nm.

[0149] <Synthesis of particle p-3> A three-neck flask was charged with 20 parts of ion-exchanged water, 0.3 parts of Rongalit (sodium hydroxymethanesulfinate), 0.01 parts of disodium ethylenediaminetetraacetate, and 0.0025 parts of ferrous sulfate heptahydrate, and the mixture was stirred at 250 rpm (revolutions per minute) at 60° C. under a nitrogen atmosphere. Next, 3.0 parts of compound A-1, 4.0 parts of compound A-2, 13.0 parts of compound B-3, 0.60 parts of sodium dodecylbenzenesulfonate, 0.58 parts of a peroxide polymerization initiator (manufactured by Nippon Oil & Fats Co., Ltd., trade name Perbutyl H), and 17 parts of ion-exchanged water were added and stirred at room temperature for 30 minutes to prepare an emulsion. 25% of the obtained emulsion was added to the three-neck flask over 30 minutes, and then heating and stirring were continued for 30 minutes, and the remaining 75% was added dropwise over 2 hours. After completion of the dropwise addition, heating and stirring were continued for 2 hours. The reaction solution was allowed to cool to room temperature (25°C) to obtain a dispersion of particles p-3 (solid content 35%). The average particle size of particles p-3 was 89 nm.

[0150] <Synthesis of particle p-4> Particles p-4 were prepared in the same manner as in the synthesis of particles p-3, except that the monomers used were changed as shown in Table 1.

[0151] <Synthesis of particle p-5> Particles p-5 were prepared in the same manner as for the synthesis of particles p-3, except that an anionic surfactant (manufactured by NOF Corporation, product name: Persoft (registered trademark) EK) was used instead of sodium dodecylbenzenesulfonate as the surfactant.

[0152] <Synthesis of particle p-6> -Synthesis of pre-coated particles p-6'- Particles p-6' were produced in the same manner as for the synthesis of particles p-3, except that the monomers used were changed as shown in Table 1. The solid content in the dispersion of particles p-6' was 35 mass %, and the average particle size of particles p-6' was 124 nm.

[0153] -Synthesis of particle p-6- Into a three-neck flask, 12.5 parts of the dispersion of particles p-6', 1.0 part of 4-hydroxybutyl acrylate glycidyl ether (E-1, 4HBAGE, manufactured by Mitsubishi Chemical Corporation), 0.2 parts of tetrabutylammonium bromide, and 30.0 parts of 1-methoxy-2-propanol were added, and the mixture was stirred at 90°C for 12 hours. The reaction solution was allowed to cool to room temperature (25°C), and a dispersion of particles p-6 (solid content 10%) was obtained. The average particle size of particles p-6 was 124 nm.

[0154] <Synthesis of particle p-7> -Synthesis of uncoated particles p-7'- Particles p-7' were produced in the same manner as for the synthesis of particles p-3, except that the monomers used were changed as shown in Table 1. The solid content in the dispersion of particles p-7' was 35 mass %, and the average particle size of particles p-7' was 85 nm.

[0155] -Synthesis of epoxy polymer E-2- 57.5 parts of 1-methoxy-2-propanol and 25.0 parts of PME-4000 (methoxypolyethylene glycol methacrylate (n = about 9), NOF Corp.) were added to a three-neck flask, and the mixture was heated to 80 ° C. under a nitrogen atmosphere and stirred at 200 rpm. A solution consisting of 37.7 parts of 4HBAGE (Mitsubishi Chemical Corp.), 2.0 parts of DPMP (dipentaerythritol hexakis (3-mercaptopropionate), SC Organic Chemical Co., Ltd.), 0.35 parts of V-601 (azobis (isobutyric acid) dimethyl, Fujifilm Wako Pure Chemical Co., Ltd.), and 40.0 parts of 1-methoxy-2-propanol was added dropwise to the three-neck flask over 2 hours, and the mixture was heated and stirred for 2 hours. Thereafter, 0.10 parts of V-601 was added, the temperature was raised to 90° C., and the mixture was reacted for 4 hours to obtain a prepolymer solution. Next, 8.5 parts of acrylic acid, 0.075 g of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (4OH-TEMPO), 1.9 parts of tetrabutylammonium bromide, and 78.0 parts of 1-methoxy-2-propanol were added to the three-neck flask and reacted at 90° C. for 24 hours to obtain a polymer solution. The weight average molecular weight of the epoxy polymer E-2 in the polymer solution was 32,000, and the solid content was 30%.

[0156] -Synthesis of particle p-7 (coating reaction)- 12.5 parts of the particle solution p-7' and 11.0 parts of ion-exchanged water were added to a three-neck flask and stirred at 75°C. 4.0 parts of the polymer solution were added dropwise over 15 minutes, and then the mixture was heated and stirred for 8 hours. The reaction solution was allowed to cool to room temperature (25°C) to obtain a dispersion of particles p-7 (solid content 20%). The average particle size of particles p-7 was 90 nm.

[0157] <Synthesis of particle p-8> -Synthesis of uncoated particles p-8'- Particles p-8' were produced in the same manner as for the synthesis of particles p-3, except that no surfactant was added and the monomers used were changed as shown in Table 1. The solid content in the dispersion of particles p-8' was 35 mass %, and the average particle size of particles p-8' was 105 nm.

[0158] -Synthesis of hydrogen-bonded polymer E-3- 42.5 parts of 1-methoxy-2-propanol were added to a three-neck flask, heated to 80° C. under a nitrogen atmosphere, and stirred at 200 rpm. A solution consisting of 30.0 parts of PME-1000 (methoxypolyethylene glycol methacrylate (n=about 23), NOF Corp.), 13.3 parts of methacrylamide (MAm), 1.7 parts of DPMP (SC Organic Chemicals Co., Ltd.), 15.5 parts of glycidyl methacrylate, 0.3 parts of V-601 (FUJIFILM Wako Pure Chemical Industries, Ltd.), and 99.0 parts of 1-methoxy-2-propanol was added dropwise to the three-neck flask over 2 hours, and heated and stirred for 2 hours. Thereafter, 0.10 parts of V-601 was added, the temperature was raised to 90° C., and the mixture was reacted for 4 hours to obtain a prepolymer solution. Next, 8.0 parts of acrylic acid, 0.07 parts of 4OH-TEMPO, 1.8 parts of tetrabutylammonium bromide, and 22.4 parts of 1-methoxy-2-propanol were added to the three-neck flask and reacted at 90° C. for 24 hours to obtain a polymer solution. The weight average molecular weight of the hydrogen-bonded polymer E-3 in the polymer solution was 29,000, and the solid content was 30%.

[0159] -Synthesis of particle p-8 (coating reaction)- A coating reaction was carried out in the same manner as in the synthesis of particles p-7, except that a polymer solution containing the hydrogen-bonded polymer E-3 was used, to obtain a dispersion of particles p-8 (solid content 20%). The average particle size of particles p-8 was 111 nm.

[0160] <Synthesis of particles p-9 and 13-18> Particles p-9 and 13 to 18 were each produced in the same manner as for particle p-3, except that the monomers used were changed as shown in Table 1.

[0161] <Synthesis of particles p-10~12> Particles p-10 to p-12 were each produced in the same manner as for particle p-7, except that the monomers used were changed as shown in Table 1.

[0162] <Synthesis of particle r-1> Particles r-1 were prepared in the same manner as in the synthesis of particles p-2, except that the monomers used were changed as shown in Table 2.

[0163] <Synthesis of particle r-2> Particles r-2 were prepared in the same manner as in the synthesis of particles p-3, except that the monomers used were changed as shown in Table 2.

[0164] <Synthesis of particle r-3> Into a four-neck flask were added 10.0 parts of compound C-1, 85.0 parts of distilled water, and 240.0 parts of n-propanol, and the mixture was heated and stirred at 70° C. under a nitrogen atmosphere. Next, a mixture of 20.0 parts of compound B-1, 70.0 parts of compound B-3, and 0.7 parts of 2,2'-azobisisobutyronitrile, which had been mixed in advance, was added dropwise over 2 hours. After the completion of the dropwise addition, the reaction was continued for 5 hours, after which 0.5 parts of 2,2'-azobisisobutyronitrile was added and the temperature was raised to 80°C. 0.4 parts of 2,2'-azobisisobutyronitrile was added every 6 hours, and the reaction was continued for a total of 19 hours. The reaction liquid was allowed to cool to room temperature (25° C.) to obtain a dispersion liquid of particles r-3 (solid content 23%). The average particle size of particles r-3 was 150 nm.

[0165] [Table 1]

[0166] [Table 2]

[0167] Details of the abbreviations in Tables 1 and 2 are as follows. In addition, the type of each unit composition is described by monomer, but in the addition polymerization type resin in the produced particles, it is the corresponding structural unit (the structural unit described above). Furthermore, the unit of the amount of each unit is parts by mass, and is the amount as a structural unit. Unit A: A structural unit having a hydrogen bond donor site Unit B: A structural unit other than structural unit A having a hydrogen bond donor site and a structural unit having a hydrophilic group Unit C: A structural unit having a hydrophilic group

[0168] A-1 to A-9 and A-12: The following compounds

[0169] [ka]

[0170] B-1 to B-5: The following compounds

[0171] [ka]

[0172] C-1 and C-2: The following compounds (n is a number described in Table 1 or Table 2).

[0173] [ka]

[0174] C-3: The following compound (C 10 ~C 14represents an alkyl group having 10 to 14 carbon atoms, and C-3 is a mixture thereof.

[0175] [ka]

[0176] <Preparation of Supports A to D> In order to remove rolling oil from the surface of an aluminum plate (material: JIS A 1050) with a thickness of 0.3 mm, the plate was degreased with a 10% by mass aqueous solution of sodium aluminate at 50°C for 30 seconds, and then it was rubbed with three bundled nylon brushes with bristles of 0.3 mm in diameter and a pumice-water suspension (specific gravity: 1.1 g / cm 3 The aluminum plate surface was grained using a 45°C etchant and thoroughly washed with water. The aluminum plate was etched by immersing it in a 25% by mass aqueous solution of sodium hydroxide at 45°C for 9 seconds, rinsing with water, and then immersed in a 20% by mass aqueous solution of nitric acid at 60°C for 20 seconds and then rinsing with water. The amount of etching on the grained surface was approximately 3 g / m 2 It was.

[0177] Next, a continuous electrochemical surface roughening treatment was performed using an AC voltage of 60 Hz. The electrolyte was a 1% by mass aqueous solution of nitric acid (containing 0.5% by mass of aluminum ions), and the temperature of the solution was 50°C. The AC power waveform was a trapezoidal rectangular AC with a duty ratio of 1:1 and a time TP from zero to the peak of the current of 0.8 msec. Electrochemical surface roughening treatment was performed using a carbon electrode as the counter electrode. Ferrite was used as the auxiliary anode. The current density was 30 A / dm at the peak value of the current. 2 The amount of electricity in nitric acid electrolysis was 175 C / dm when the aluminum plate was the anode. 2 After that, the surface was washed with water using a spray.

[0178] Next, in an electrolyte solution of 0.5 mass% hydrochloric acid (containing 0.5 mass% aluminum ions) at a temperature of 50°C, the aluminum plate was charged with a quantity of electricity of 50 C / dm 2Under the above conditions, electrochemical surface roughening treatment was performed in the same manner as in the nitric acid electrolysis, and then washing with water was performed by spraying. Next, a 15% by mass sulfuric acid aqueous solution (containing 0.5% by mass of aluminum ions) was used as the electrolyte on the aluminum plate, and a current density of 15 A / dm 2 2.5g / m 2 After forming the DC anodized film, it was washed with water and dried to prepare Support A. The average pore diameter in the surface layer of the anodized film (surface average pore diameter) was 10 nm. The pore diameters on the surface layer of the anodized film were measured using an ultra-high resolution scanning electron microscope (SEM) (S-900 manufactured by Hitachi, Ltd.) at a relatively low acceleration voltage of 12 V. The surface was observed at a magnification of 150,000 times, without any deposition treatment to impart conductivity, and 50 pores were randomly selected to calculate the average value. The standard deviation error was within ±10%.

[0179] Thereafter, in order to ensure the hydrophilicity of the non-image area, support A was subjected to a silicate treatment using a 2.5% by weight aqueous solution of sodium silicate No. 3 at 60°C for 10 seconds, and then washed with water to prepare support B. The amount of silicon attached was 10 mg / m 2 The center line average roughness (Ra) of the support B was measured using a needle with a diameter of 2 μm and was found to be 0.51 μm.

[0180] Support C was produced in the same manner as Support A, except that the electrolytic solution used in forming the DC anodized film was changed to a 22 mass% aqueous phosphoric acid solution. The average pore diameter (surface average pore diameter) in the surface layer of the anodized film was measured by the same method as above and was found to be 25 nm.

[0181] Thereafter, in order to ensure the hydrophilicity of the non-image area, Support C was subjected to a silicate treatment using a 2.5% by weight aqueous solution of sodium silicate No. 3 at 60°C for 10 seconds, and then washed with water to prepare Support D. The amount of silicon attached was 10 mg / m 2 The center line average roughness (Ra) of the support D was measured using a needle with a diameter of 2 μm and was found to be 0.52 μm.

[0182] <Preparation of Support E> An aluminum alloy plate of material 1S having a thickness of 0.3 mm was subjected to (Aa) mechanical roughening treatment (brush grain method) described in paragraph 0126 of JP2012-158022A to (Ai) desmutting treatment in an acidic aqueous solution described in paragraph 0134 of JP2012-158022A. Next, the conditions of the first anodizing treatment (Aj) described in paragraph 0135 to the third anodizing treatment (Am) described in paragraph 0138 of JP2012-158022A are appropriately adjusted, An anodized coating was formed having large pores with an average diameter of 35 nm and a depth of 100 nm and small pores with an average diameter of 10 nm and a depth of 1,000 nm, with the ratio of the depth of the large pores to the average diameter of the large pores being 2.9, to obtain aluminum support E. In addition, water washing treatment was carried out between all processing steps, and after the water washing treatment, the liquid was removed by using nip rollers.

[0183] (Examples 1 to 23 and Comparative Examples 1 to 4) <Formation of undercoat layer> On the support shown in Table 3 or Table 4, the undercoat layer coating solution (1) having the following composition was applied in a dry coating amount of 20 mg / m 2 The undercoat layer was formed by coating so as to become

[0184] - Undercoat layer coating solution (1) - Polymer (P-1) [structure below]: 0.18 parts Hydroxyethyliminodiacetic acid: 0.10 parts ·Wednesday: 61.4 parts

[0185] [ka]

[0186] <Preparation of lithographic printing plate precursor> The lithographic printing plate precursors of Examples 1 to 13 and Comparative Examples 1 to 4 were each prepared by the following method. Each image recording layer coating solution (solid content 6%) having the composition shown in Table 3 or Table 4 was applied onto the undercoat layer with a bar, and dried in an oven at 120°C for 40 seconds to obtain a dry coating amount of 1.0 g / m 2 Thus, an image recording layer of If necessary, the protective layer coating solution having the above composition is applied onto the image recording layer with a bar, and dried in an oven at 120° C. for 60 seconds to obtain a dry coating amount of 0.15 g / m 2 A protective layer of For the examples in which a protective layer was formed, the column for protective layer in Table 3 or Table 4 states "Yes."

[0187] <Formation of protective layer> A protective layer coating solution having the following composition was applied onto the image recording layer with a bar, and dried in an oven at 120°C for 60 seconds to obtain a dry coating weight of 0.15 g / m 2 A protective layer of

[0188] -Protective layer coating solution- Inorganic layered compound dispersion (1) [below]: 1.5 parts Polyvinyl alcohol (CKS50, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., sulfonic acid modified, saponification degree 99 mol% or more, polymerization degree 300) 6 mass% aqueous solution: 0.55 parts Polyvinyl alcohol (PVA-405, manufactured by Kuraray Co., Ltd., saponification degree 81.5 mol%, polymerization degree 500) 6 mass% aqueous solution: 0.03 parts Surfactant (polyoxyethylene lauryl ether, Emalex 710, manufactured by Nippon Emulsion Co., Ltd.) 1% by weight aqueous solution: 0.86 parts Ion-exchanged water: 6.0 parts

[0189] The method for preparing the inorganic layered compound dispersion (1) is described below.

[0190] <Preparation of Inorganic Layered Compound Dispersion (1)> 6.4 parts of synthetic mica (Somasif ME-100, manufactured by Co-op Chemical Co., Ltd.) was added to 193.6 parts of ion-exchanged water, and dispersed using a homogenizer until the average particle size (laser scattering method) became 3 μm. The aspect ratio of the obtained dispersed particles was 100 or more.

[0191] <Evaluation of lithographic printing plate precursors> [UV printing durability] The lithographic printing plate precursor prepared as described above was exposed to light (irradiation energy 110 mJ / cm) using a Kodak Magnus800 Quantum equipped with an infrared semiconductor laser under the conditions of an output of 27 W, an outer drum rotation speed of 450 rpm, and a resolution of 2,400 dpi (dots per inch, 1 inch is 2.54 cm). 2 The exposure image included a solid image and an AM screen (Amplitude Modulated Screening) 3% halftone dot chart. The exposed plate thus obtained was attached to the cylinder of a Heidelberg SX-74 printing press of the 1900 format without development. A 100 L dampening water circulating tank with a built-in nonwoven fabric filter and temperature control device was connected to this printing press. 80 L of 2.0% dampening water S-Z1 (FUJIFILM Corporation) was charged into the circulating device, and T&K UV OFS K-HS ink GE-M (T&K TOKA Corporation) was used as the printing ink. After supplying the dampening water and ink using the standard automatic printing start method, printing was performed on Tokubishi Art paper (Mitsubishi Paper Mills, ream weight: 76.5 kg) at a printing speed of 10,000 sheets per hour. As the number of prints increased, the image area gradually wore away, causing the ink density on the prints to decrease. Printing durability was evaluated as the number of prints completed when the dot area ratio of the AM screen 3% dots on the prints, measured with a Gretag densitometer (manufactured by GretagMacbeth), fell 1% from the value measured on the 500th print. Relative printing durability was evaluated, with 50,000 prints being taken as 100. The higher the value, the better the UV printing durability. Relative printing durability = (number of prints of the target lithographic printing plate precursor) / 50,000 x 100

[0192] [Scratch resistance] A continuous load scratch resistance tester Type: 18 (manufactured by Shinto Scientific Co., Ltd.) was used. Scratch resistance test: A 3 cm scratch test was performed with a sapphire needle (r0.03 mm) at a load of 200 g and a moving speed of 600 mm / min, referring to ISO 12137-2-1997. After performing the scratch test in 10 places on the image area of ​​each sample, exposure and printing were performed under the conditions of the UV printing durability test described above, and the number of linear chips that appeared in the image area on the 2,000th printed sheet was counted. The fewer the chips, the better the scratch resistance.

[0193] [Table 3]

[0194] [Table 4]

[0195] From the results shown in Tables 3 and 4, it is clear that the lithographic printing plate precursors according to the present disclosure shown in the Examples have superior UV printing durability compared to the lithographic printing plate precursors of the Comparative Examples. Furthermore, the results shown in Tables 3 and 4 show that the lithographic printing plate precursors according to the present disclosure shown in the examples also have excellent scratch resistance.

[0196] In Table 3, * indicates that the tetraphenylborate anion is contained from K-2 and I-2. Further, details of each compound listed in Table 3 or Table 4 other than those mentioned above are shown below.

[0197] [Infrared absorbing agent] K-1 to K-3: Compounds having the following structures

[0198] [ka]

[0199] In the above structure, Ph represents a phenyl group.

[0200] [Electron-accepting polymerization initiator] I-1 to I-3: Compounds having the following structures

[0201] [ka]

[0202] In the above structure, TsO - represents a tosylate anion.

[0203] [Electron-donating polymerization initiator (polymerization aid)] J-1 to J-5: Compounds having the following structures

[0204] [ka]

[0205] In the above structure, Ph represents a phenyl group and Bu represents a butyl group.

[0206] [Acid color former] H-1: S-205 (Fukui Yamada Chemical Industry Co., Ltd.) H-2: GN-169 (Yamamoto Chemical Industry Co., Ltd.) H-3: Black-XV (Yamamoto Chemical Industry Co., Ltd.) H-4: Red-40 (Yamamoto Chemicals Co., Ltd.)

[0207] [Polymerizable compound] M-1: Tris(acryloyloxyethyl)isocyanurate, NK Ester A-9300, manufactured by Shin-Nakamura Chemical Co., Ltd. M-2: Dipentaerythritol pentaacrylate, SR-399, manufactured by Sartomer Corporation M-3: Dipentaerythritol hexaacrylate, A-DPH, manufactured by Shin-Nakamura Chemical Co., Ltd. M-4: Dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, UA-510H, manufactured by Kyoeisha Chemical Co., Ltd. M-5: Ethoxylated pentaerythritol tetraacrylate, ATM-4E, manufactured by Shin-Nakamura Chemical Co., Ltd.

[0208] [High molecular compound] Polymer compound BI-1 (structure below, Mw: 35,000, n=2 (number of EO units))

[0209] [ka]

[0210] [Polymer particles] G-1: Microgel (1) below. Note that the image recording layer coating liquid containing polymer particles G-1 (microgel (1)) was prepared by mixing a composition containing the components listed in Table 3 other than the microgel liquid below with the microgel liquid below just before coating and stirring to obtain the composition listed in Table 3.

[0211] -Preparation of microgel solution- Microgel (1) (polymer particles G-1): 2.640 parts Distilled water: 2.425 parts

[0212] The method for preparing the microgel (1) used in the above microgel solution is described below.

[0213] -Preparation of polyisocyanate compound (1)- To a suspension of 17.78 g (80 mmol) of isophorone diisocyanate and 7.35 g (20 mmol) of the following polyhydric phenol compound (1) in ethyl acetate (25.31 g), 43 mg of bismuth tris(2-ethylhexanoate) (Neostan U-600, manufactured by Nitto Kasei Co., Ltd.) was added and stirred. When the heat generation subsided, the reaction temperature was set to 50° C., and the mixture was stirred for 3 hours to obtain an ethyl acetate solution (50% by mass) of the polyhydric isocyanate compound (1).

[0214] [ka]

[0215] -Preparation of microgel (1)- The following oil phase components and water phase components were mixed and emulsified for 10 minutes at 12,000 rpm using a homogenizer. The resulting emulsion was stirred at 45°C for 4 hours, and then 5.20 g of a 10% by mass aqueous solution of 1,8-diazabicyclo[5.4.0]undec-7-ene-octylate (U-CAT SA102, San-Apro Co., Ltd.) was added, stirred at room temperature for 30 minutes, and allowed to stand at 45°C for 24 hours. The solid content was adjusted to 20% by mass with distilled water, and an aqueous dispersion of microgel (1) was obtained. The average particle size was measured by a light scattering method and found to be 0.28 μm.

[0216] ~Oily phase components~ (Component 1) Ethyl acetate: 12.0 parts (Component 2) 3.76 parts of an adduct (50% by mass in ethyl acetate solution, manufactured by Mitsui Chemicals, Inc.) obtained by adding trimethylolpropane (6 molar equivalents) and xylylene diisocyanate (18 molar equivalents) to which methyl-terminated polyoxyethylene (1 molar equivalent, number of repeating oxyethylene units: 90) was added. (Component 3) Polyisocyanate compound (1) (as a 50% by mass solution in ethyl acetate): 15.0 parts (Component 4) 65% by weight solution of dipentaerythritol pentaacrylate (SR-399, manufactured by Sartomer Corporation) in ethyl acetate: 11.54 parts (Component 5) 10% ethyl acetate solution of sulfonate surfactant (Paionin A-41-C, Takemoto Oil Co., Ltd.): 4.42 parts

[0217] ~Aqueous phase components~ Distilled water: 46.87 parts

[0218] [Hydrophilic compound] T-1: Tris(2-hydroxyethyl)isocyanurate T-2: Compound having the following structure T-3: Hydroxypropyl cellulose, Klucel M, manufactured by Hercules

[0219] [ka]

[0220] [Oil Sensitizer] CL-1: Compound having the following structure CL-2: Benzyldimethyloctylammonium·PF6 salt CL-3: Compound having the following structure

[0221] [ka]

[0222] 〔solvent〕 S-1: 2-butanone (MEK) S-2: 1-Methoxy-2-propanol (MFG) S-3: Methanol S-4: 1-propanol S-5: Distilled water

[0223] The disclosure of Japanese Patent Application No. 2019-016540, filed on January 31, 2019, is incorporated herein by reference in its entirety. All publications, patent applications, and technical standards mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent application, or technical standard was specifically and individually indicated to be incorporated by reference.

Claims

1. A support, and An image recording layer is provided on the support, the image recording layer comprises organic particles containing an addition polymerization resin having a structural unit A having a hydrogen bond donor site selected from the group consisting of A-1, A-2, A-3, A-4, A-5, A-6, A-7, A-8, A-9, and A-12 below, a structural unit having an aromatic ring selected from the group consisting of B-1, B-2, and B-4 below, and a structural unit having a hydrophilic group selected from the group consisting of C-1, C-2, and C-3 below, an infrared absorbing agent, a polymerization initiator, and a polymerizable compound; a content of the structural unit A in the addition polymerization resin is 25% by mass or more, based on a total mass of the addition polymerization resin, and a content of the structural unit having an aromatic ring in the addition polymerization resin is 10% by mass to 75% by mass, based on the total mass of the addition polymerization resin. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 In formula C-1, n represents an integer of 24 to 90. 【Chemistry 4】 In formula C-3, C 10 ~C 14 represents an alkyl group having 10 to 14 carbon atoms, and C-3 is a mixture thereof.

2. The lithographic printing plate precursor for on-press development according to claim 1, wherein the organic particles have a volume average particle size of 10 nm to 10,000 nm.

3. The lithographic printing plate precursor for on-press development according to claim 1 or 2, wherein the organic particles have a volume average particle size of 70 nm to 200 nm.

4. The lithographic printing plate precursor for on-press development according to any one of claims 1 to 3, wherein the hydrophilic group is a group having a polyalkylene oxide structure.

5. The lithographic printing plate precursor for on-press development according to any one of claims 1 to 3, wherein the hydrophilic group is a sulfonate salt group or a sulfonic acid group.

6. The lithographic printing plate precursor for on-press development according to any one of claims 1 to 5, wherein a content of the structural unit having a hydrophilic group in the addition polymerization type resin is 1% by mass to 20% by mass with respect to a total mass of the addition polymerization type resin.

7. The lithographic printing plate precursor for on-press development according to any one of claims 1 to 6, wherein the organic particles comprise organic particles having an ethylenically unsaturated group on the surface thereof.

8. The lithographic printing plate precursor for on-press development according to any one of claims 1 to 7, wherein the image recording layer further comprises a binder polymer.

9. The lithographic printing plate precursor for on-press development according to any one of claims 1 to 8, further comprising a protective layer on the image recording layer.

10. The lithographic printing plate precursor for on-press development according to claim 9 , wherein the protective layer contains an inorganic layered compound.

11. The lithographic printing plate precursor for on-press development according to any one of claims 1 to 10, wherein the image recording layer is a negative image recording layer.

12. The lithographic printing plate precursor for on-press development according to any one of claims 1 to 11, wherein the image recording layer is an on-press development type image recording layer.

13. A step of imagewise exposing the lithographic printing plate precursor for on-press development according to any one of claims 1 to 12; and a step of removing the image recording layer in the non-image area on the printing press by supplying at least one selected from the group consisting of printing ink and dampening water. How to make a lithographic printing plate.

14. A step of imagewise exposing the lithographic printing plate precursor for on-press development according to any one of claims 1 to 12; a step of removing the image recording layer in the non-image area on the printing press by supplying at least one selected from the group consisting of printing ink and dampening water to prepare a lithographic printing plate; and printing with the resulting lithographic printing plate. Lithographic printing method.

Citation Information

Patent Citations

  • Lithographic printing plate material and image forming method

    JP2007001112A

  • Photosensitive resin composition, pattern-forming material, image forming method, lithographic printing plate precursor and method for producing the lithographic printing plate

    JP2008185729A

  • Polymerizable composition and lithographic printing plate precursor

    JP2012211938A

  • Copolymers for radiation-sensitive coating compositions for negative radiation-sensitive lithographic printing plates, polymer particles containing the copolymer, and copolymer binders

    JP2013504632A

  • Lithographic printing method using a single fluid ink

    US20040094057A1